Biodegradable microcapsules and methods for their preparation

By regulating the solubility of proteins in plant-source protein solutions using soluble co-solvents, promoting gel formation and shear treatment to prepare microcapsules, the instability of microcapsules under acidic or alkaline conditions in the prior art is solved, and the stability and adaptability in liquid products are achieved.

JP2025508021APending Publication Date: 2025-03-21XAMPLA LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024553164
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-08
Filing Date
2023-03-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to prepare biodegradable microcapsules that are stable under water, acidic or alkaline conditions, and the traditional methods are insufficient in adaptability to liquid product forms.

Method used

By forming a solution containing plant-sourced proteins, the solubility of the protein is increased by soluble cosolvents, and by degrading the cosolvent, its solubility is reduced, the protein is promoted for gel transfer, forming a gel, and then shear treatment is made to form microcapsules, and the active ingredients are spread therein, and the microcapsules are finally prepared by drying.

Benefits of technology

Prepare biodegradable microcapsules that are stable in liquid products to ensure the protection of the active ingredients during production and storage, and maintain structural integrity under applicable conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025508021000001_ABST
    Figure 2025508021000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing microcapsules and a method for preparing a microcapsule composition. The present invention also relates to the microcapsules and the microcapsule composition itself. The present invention also relates to the use of the microcapsules and methods involving the microcapsules, including preparing a formulated product. The present invention also relates to the formulated product itself.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for preparing biodegradable microcapsules and a method for preparing a biodegradable microcapsule composition. The present invention also relates to the biodegradable microcapsules and the biodegradable microcapsule composition itself. The present invention also relates to the use of the biodegradable microcapsules and methods involving the biodegradable microcapsules, including preparing a formulated product. The present invention also relates to the formulated product itself. [Background technology]

[0002] Encapsulation techniques, which involve embedding an active ingredient in an external matrix, can be used to protect the active ingredient from its external environment (e.g., exposure to chemicals, air, light, etc.) and also to protect the external environment from the active ingredient itself, such as when handling is hazardous. For example, this allows the active ingredient to be protected when added to a product formulation (e.g., beverage formulation, fabric conditioner formulation, etc.), meaning that the active ingredient in the product formulation has an acceptable shelf life and / or does not activate prematurely. This also means that the external phase of the product formulation is not adversely affected by the active ingredient. The active ingredient is then released when needed (e.g., upon breakage of the encapsulate or upon enzymatic degradation of the encapsulate).

[0003] Many commonly available encapsulation techniques are based on the use of synthetic polymers to form a protective shell around active ingredients.However, synthetic polymers may not be suitable as carriers in pharmaceutical and food applications, or may have limited acceptable exposure levels in cosmetic applications.In addition, synthetic polymer shell materials may lead to the formation of microplastics, which are harmful to the environment.

[0004] Spray drying techniques allow for the large-scale preparation of microcapsules, and spray drying of plant proteins has been attempted to achieve the production of biodegradable microcapsules. However, in order to achieve robust microcapsules of sufficiently small size via spray drying techniques, the material to be spray dried must have low viscosity at high shear rates (e.g., the material must be shear thinning to a sufficiently low viscosity for good spray drying to occur) and also have a sufficiently high protein solids content. Conventional methods for preparing plant protein-based materials suitable for spray drying involve hydrolyzing the protein (e.g., via treatment with acid or alkali or enzymes) to break it down into lower molecular weight fragments. However, the resulting spray-dried microcapsules are not structurally stable in water or under acidic or alkaline conditions, at high temperatures, and / or under high shear forces, which means that they are not suitable for incorporation into product formulations, particularly liquid product formulations, via common manufacturing processes. Furthermore, many oils are unstable under alkaline conditions, so the processes involved may have adverse effects on the material to be encapsulated.

[0005] Thus, there is a need for a method of preparing active ingredient-containing microcapsules that are small enough in size to be incorporated into liquid product formulations, and that are biodegradable and stable in the liquid product formulations (i.e., the microcapsules retain their structural integrity under either acidic or alkaline conditions such that the active ingredient is protected during manufacturing and throughout the shelf life of the product). Summary of the Invention

[0006] Viewed from a first aspect, the present invention provides a method for the preparation of biodegradable microcapsules, comprising: (a) forming a solution comprising one or more plant-derived proteins in a solvent system, the solvent system comprising miscible co-solvents, a first co-solvent increasing the solubility of the plant-derived proteins and a second co-solvent decreasing the solubility of the plant-derived proteins; (b) inducing the plant-derived protein in solution to undergo a sol-gel transition to form a plant-derived protein hydrogel; (c) subjecting the plant-derived protein hydrogel to a shear treatment to form a plant-derived protein hydrogel slurry; (d) dispersing an active ingredient in the plant-derived hydrogel slurry to form a composition; (e) drying the composition to form microcapsules.

[0007] Viewed from a further aspect, the present invention provides biodegradable microcapsules obtained or obtainable by the process described above.

[0008] Viewed from a further aspect, the present invention provides a method for the preparation of a biodegradable microcapsule composition, comprising the steps of: (a) preparing biodegradable microcapsules according to the method described above; (b) suspending the biodegradable microcapsules in the external phase.

[0009] Viewed from a further aspect, the present invention provides a biodegradable microcapsule composition obtained or obtainable by the process described above.

[0010] Viewed from a further aspect, the present invention provides a biodegradable microcapsule comprising an active ingredient and a plant derived protein carrier comprising a plant derived protein, the plant derived protein carrier encapsulating the active ingredient, and the plant derived protein having a solubility of less than 50% when measured at a protein concentration of 5% w / w in aqueous solution at pH 7 and 25°C.

[0011] Viewed from a further aspect, the present invention provides a composition comprising a biodegradable microcapsule as described above and an external phase.

[0012] Viewed from a further aspect, the present invention provides a formulated product comprising the biodegradable microcapsules described above.

[0013] Viewed from a further aspect, the present invention provides a method for producing ... composition comprising the steps of: (a) preparing biodegradable microcapsules according to the method described above; (b) mixing the biodegradable microcapsules with a product formulation.

[0014] Viewed from a further aspect, the present invention provides the use of the biodegradable microcapsules described above in a formulated product.

[0015] definition As used herein, the term "microcapsule" refers to any form of microparticle. For example, the term includes core-shell microcapsules (i.e., microcapsules having a central core containing an active ingredient, the core being surrounded by a plant-derived protein hydrogel in the form of a shell). As will be appreciated by those skilled in the art, core-shell microcapsules may have a multicore morphology (i.e., the core phase is in the form of multiple droplets) or a single-core morphology (the core phase is in the form of a single droplet). The term also includes matrix microcapsules (i.e., microcapsules composed of a plant-derived protein hydrogel matrix with an active ingredient dispersed throughout). Microcapsules have a diameter of 500 nm to 2 mm as measured by laser diffraction. 50 may have:

[0016] As used herein, the term "lower shear process" may refer to a process step in which low levels of mechanical energy are applied to a material, preferably by a cutting action, to break or fragment it primarily into large separate fragments. "Low shear" typically refers to high velocity impacts, e.g., less than 2 ms -1The present invention does not include any comminution process that crushes or fragments a material by impact with a velocity difference exceeding 1 mm. It also typically does not include cavitation-based milling processes. In certain embodiments, during the low shear process, the hydrogel is fragmented to obtain fragments such that at least 80% by weight of the hydrogel fragments have a maximum dimension of between 1 mm and 100 mm as measured by optical microscopy.

[0017] As used herein, the term "higher shear step" may refer to a process step in which energy is applied to reduce a hydrogel into small fragments, such as to form a colloidal dispersion. In certain embodiments, during the higher shear step, the hydrogel is fragmented to a size of 0.5 to 50 microns d as measured by laser diffraction. 50 This gives fragments having a particle size. Laser diffraction can be carried out according to the methods defined herein.

[0018] For the avoidance of doubt, the high shear step subjects the hydrogel to a higher level of shear than the low shear step. If the process involves both a low shear step and a high shear step, the high shear step must occur after the low shear step (i.e., they are separate steps occurring in this particular order).

[0019] As used herein, the term "sol-gel transition temperature" refers to the temperature at which the plant-derived protein transforms from a liquid state to a hydrogel state. Thus, at temperatures above the sol-gel transition temperature, the plant-derived protein is in a liquid state, and at temperatures below the sol-gel transition temperature, the plant-derived protein is in a hydrogel state.

[0020] As used herein, "fragrance" (used interchangeably with the term "perfume") refers to a component of a formulation that can impart or modify the odor of a product, such as a fabric or hair conditioner, or the odor of a substrate, such as fabric or hair. Fragrances are typically used to impart an overall pleasant odor or odor profile to a product to provide a pleasant experience, e.g., fine fragrances, or to provide sensory cues regarding the benefits and functionality of the product, e.g., the calming effect of a lavender sleep aid, the idea of ​​cleanliness in laundry products, or to mask unpleasant odors, such as in insect repellent products. A "fragrance" can be composed of one or more ingredients, which can be a single chemical, referred to herein as a "fragrance material" (used interchangeably with the term "perfume material"), or a mixture of different "fragrance materials". Fragrance materials can be created by synthetic processes or extracted from nature, particularly plants, to obtain naturally occurring plant essential oils and plant extracts, e.g., orange oil. Fragrance materials created by synthetic processes can be either entirely new chemicals or nature-identical fragrance materials. The synthetic and naturally derived fragrance materials can then be blended into fragrances by skilled perfumers (also called noses) for use in consumer products. Fragrance materials can be obtained from specialized fragrance suppliers known as fragrance houses as individual chemicals, natural blends, or as proprietary specialty blends whose complete composition is not disclosed.Individual fragrance materials, including known natural blends, can be found by consulting journals commonly used by those skilled in the art, such as "Perfume and Flavourist" or "Journal of Essential Oil Research", or journals listed in reference books such as S. Arctander Perfume and Flavor Chemicals, 1969, Montclair, New Jersey, USA, and more recently republished by Allured Publishing Corporation Illinois (1994) and "Perfume and Flavour Materials of Natural Origin", S. Arctander, Ed., Elizabeth, NJ, 1960. For the purposes of the present invention, "fragrance material" will be understood to include profragrances, such as acetal profragrances, ketal profragrances, ester profragrances, hydrolyzable inorganic-organic profragrances, and combinations thereof. The fragrance material may be released from the profragrances in any number of ways, for example, by hydrolysis, or by a shift in an equilibrium reaction, or by a pH change, or by enzyme release, or by UV radiation.

[0021] Fragrance materials can be described in terms of their odor intensity, detection threshold, odor saturation, and their characteristics. In fragrance encapsulations, it is preferable to use fragrance materials with low odor detection thresholds and high intensity so as to maximize detectability even with small levels of encapsulated and released fragrance.

[0022] To impart an odor, fragrance materials must be volatile, even if only to a small extent, because they must be airborne and enter the nose where they attach to specific neuroreceptors and trigger signals within the olfactory system. Fragrance materials can be classified according to their volatility. Preferably, fragrance materials are liquid at 20° C. and atmospheric pressure, but in some cases they may be solid and can be blended with other liquid fragrance materials or solvents. Typically, the fragrance industry refers to volatility and persistence by broadly classifying materials into one of three categories: base notes, which are the least volatile and most persistent; heart notes, which are medium volatile and persistent; and top notes, which are the most volatile and least persistent. This is based on the perception of the odor of the material and is entirely subjective. One way to objectively classify the volatility of fragrance materials is by their vapor pressure.

[0023] As used herein, the term "vapor pressure" refers to the partial pressure in air at a specified temperature (e.g., 25°C) and standard atmospheric pressure (760mmHg) for a given chemical species. It defines the affinity of a chemical species for the gas phase rather than the liquid or solid state. The higher the vapor pressure, the greater the proportion of the material present in a closed headspace at equilibrium. It is also related to the evaporation rate of the fragrance material, defined in an open environment where the material leaves the system. Vapor pressure can be readily determined according to the reference program ACD / Percepta Desktop Software, Version 14.0 (Build: Aug / 26 / 2021), Advanced Chemistry Development, Inc (ACD / Labs), Toronto, Canada, www.acdlabs.com.

[0024] A physical parameter relevant to the encapsulation of a fragrance material is its hydrophobicity, which can be defined in terms of its partition coefficient P. As used herein, the term "partition coefficient" refers to the ratio between the equilibrium concentration of the substance in n-octanol and in water, and is a measure of the differential solubility of the substance between these two solvents. As used herein, the term "logP" refers to the base 10 logarithm of the partition coefficient P. logP can be easily determined according to the reference program ACD / Percepta Desktop Software, Version 14.0 (Build: Aug / 26 / 2021), Advanced Chemistry Development, Inc (ACD / Labs), Toronto, Canada, www.acdlabs.com. The logP value is predicted from the SMILE string of the fragrance material molecule. Three different types of logP values ​​can be selected from the software. logP Classic is based on an algorithm that takes into account a database of experimental logP values ​​while using the principle of isolating carbon. logP GALAS is based on an algorithm that takes into account a database of training sets of compounds and adjusts the values ​​with data from structurally similar compounds. Consensus logP is a model based on the previous two algorithms and can be expressed as Consensus logP = a x logP Classic + b x logP GALAS, where a and b are the coefficients of the model. The latter value, Consensus logP, is the logP value shown in this specification.

[0025] Another aspect related to the encapsulation of a fragrance material is its Hansen Solubility Parameter (HSP). The term HSP refers to the solubility parameter approach proposed by Charles Hansen, which was first used to predict polymer solubility in a given solvent, as described in The Three Dimensional Solubility Parameter and Solvent Diffusion Coefficient, by Charles Hansen, Danish Technical Press (Copenhagen, 1967). This approach has since been reapplied to many other molecules. A fragrance material (or flavor material or solvent) and its interaction with its environment are defined by three forces: atomic dispersion forces, molecular permanent dipole forces, and molecular hydrogen bond forces. Materials with similar HSP parameters are more likely to be miscible. These forces can be quantified by three values: δD, the Hansen dispersion value related to van der Waals interactions (intermolecular forces); δP, the Hansen polarity value related to dipole moments (charges); and δH, the Hansen hydrogen bond ("h-bond") value. Solubility parameter δ(MPa 1 / 2 ) is δ 2 = δ D 2+ δ P 2+ δ H 2=E / V, where E is the cohesive energy of the solvent and V is the molar volume. HSP values ​​for a given material can be obtained in two main different ways from the Hansen Solubility Parameters in Practice (HSPiP) software available at www.hansen-solubility.com. These values ​​can be retrieved from the Master Dataset, which contains over 20,000 materials, by searching by name or CAS number, or they are predicted by entering the SMILE string of a given molecule in the DIY section of the software using the Yamamoto-Molecular Breaking (Y-MB) method. Furthermore, the determination of the HSP sphere for a given fragrance material is a good way to predict the solubility preference within a blend of fragrance materials. The radius of the HSP sphere, Ro, is defined as Ro=Ra / RED, where Ra is the cohesive energy of the solvent and V is the molar volume. 2= 4(δ D1 -δ D2 ) 2+ (δ P1 -δ P2 ) 2 +(δ H1 -δ H2 ) 2 where RED is the relative energy difference between two molecules (1 and 2) and RED is the HSP distance between the two molecules (1 and 2). This RED value can also be extracted or predicted from the HSPiP software, and a good solvent for a given material should exhibit a RED value of 1 or less, while a solvent exhibiting a RED value greater than 1 should be considered a poor solvent for the given material.

[0026] The fragrance materials may be selected from alcohols, aldehydes, ketones, esters, ethers, acetates, alkenes, nitriles, nitrogen heterocycles, sulfur heterocycles, and Schiff bases.

[0027] Preferred aldehyde fragrance materials include alpha-amylcinnamaldehyde, anisaldehyde, decyl aldehyde, lauric aldehyde, methyl n-nonylacetaldehyde, methyl octylacetaldehyde, nonyl aldehyde, benzenecarboxaldehyde, neral, geranial, 1,1-diethoxy-3,7-dimethylocta-2,6-diene, 4-isopropylbenzaldehyde, 2,4-dimethyl-3-cyclohexene-1-carboxylate, 1,2-dimethyl-2,3-dimethyl-1,4-dimethyl-1,5-dimethyl-1,6-dimethyl-1,7-dimethyl-1,8-dimethyl-1,9-dimethyl-1,8-dimethyl-1,9-dimethyl-1,9-dimethyl-1,5-dimethyl-1,8-dimethyl-1,9 ... cinnamaldehyde, alpha-methyl-p-isopropyldihydrocinnamaldehyde, 3-(3-isopropylphenyl)butanal, alpha-hexylcinnamaldehyde, 7-hydroxy-3,7-dimethyloctan-1-al, 2,4-dimethyl-3-cyclohexene-1-carboxaldehyde, octylaldehyde, phenylacetaldehyde, 2,4-dimethyl-3-cyclohexene-1-carboxaldehyde, hexanal, 3,7-dimethyloctanal, 6,6-dimethylbicyclo[3. 1.1]hept-2-ene-2-butanal, nonanal, octanal, 2-nonenal, undecenal, 2-methyl-4-(2,6,6-trimethyl-1-cyclohexenyl-1)-2-butenal, 2,6-dimethyloctanal, 3-(p-isopropylphenyl)propionaldehyde, 3-phenyl-4-pentenal, citronellal, o / p-ethyl-alpha, alpha, 9-decenal, dimethyldihydrocinnamaldehyde, p-isobutyl-alpha, methylhydrocinnamaldehyde , cis-4-decen-1-al, 2,5-dimethyl-2-ethenyl-4-hexenal, trans-2-methyl-2-butenal, 3-methylnonanal, alpha-sinensal, 3-phenylbutanal, 2,2-dimethyl-3-phenylpropionaldehyde, m-tertbutyl-alpha-methyldihydrocinnamic aldehyde, geranyloxyacetaldehyde, trans-4-decen-1-al, methoxycitronellal, and mixtures thereof.

[0028] Preferred ester fragrance materials include allyl cyclohexane propionate, allyl heptanoate, allyl amyl glycolate, allyl caproate, amyl acetate (n-pentyl acetate), amyl propionate, benzyl acetate, benzyl propionate, benzyl salicylate, cis-3-hexenyl acetate, citronellyl acetate, citronellyl propionate, cyclohexyl salicylate, dihydroisojasmonate, Dimethylbenzylcarbinyl acetate, ethyl acetate, ethyl acetoacetate, ethyl butyrate, ethyl 2-methylbutyrate, ethyl 2-methylpentanoate, fenchyl acetate (1,3,3-trimethyl-2-norbornanyl acetate), tricyclodecenyl acetate, tricyclodecenyl propionate, geranyl acetate, cis-3-hexenyl isobutyrate, hexyl acetate, cis-3-hexenyl salicylate, n- Hexyl salicylate, isobornyl acetate, linalyl acetate, para-tert-butylcyclohexyl acetate, (-)-L-menthyl acetate, ortho-tert-butylcyclohexyl acetate, methyl benzoate, methyl dihydroisojasmonate, alpha-methylbenzyl acetate, methyl salicylate, 2-phenylethyl acetate, prenyl acetate, cedryl acetate, cyclabute, phenethyl phenyl acetate , terpinyl formate, citronellyl anthranilate, ethyl tricyclo[5.2.1.0-2,6]decane-2-carboxylate, n-hexyl ethyl acetoacetate, 2-tert-butyl-4-methylcyclohexyl acetate, formic acid, 3,5,5-trimethylhexyl ester, phenethyl crotonate, cyclogeranyl acetate, geranyl crotonate, ethyl geranate, geranyl isobutyrate, 3,7-dimethylethyl 2-noninoate-2,6-Octadienoic acid methyl ester, citronellyl valerate, 2-hexenyl cyclopentanone, cyclohexyl anthranilate, L-citronellyl tiglate, butyl tiglate, pentyl tiglate, geranyl caprylate, 9-decenyl acetate, 2-isopropyl-5-methylhexyl-1-butyrate, n-pentyl benzoate, 2-methylbutyl benzoate (and mixtures thereof with pentyl benzoate), dimethylbenzyl carbinyl propionate, dimethylbenzyl carbinyl Acetate, trans-2-hexenyl salicylate, dimethylbenzylcarbinyl isobutyrate, 3,7-dimethyloctyl formate, rosinyl formate, rosinyl isovalerate, rosinyl acetate, rosinyl butyrate, rosinyl propionate, cyclohexyl ethyl acetate, neryl butyrate, tetrahydrogeranyl butyrate, myrcenyl acetate, 2,5-dimethyl-2-ethenylhex-4-enoic acid methyl ester, 2,4-dimethylcyclohexane-1-methyl acetate tate, ocimenyl acetate, linalyl isobutyrate, 6-methyl-5-heptenyl-1-acetate, 4-methyl-2-pentyl acetate, n-pentyl 2-methylbutyrate, propyl acetate, isopropenyl acetate, isopropyl acetate, 1-methylcyclohex-3-ene-carboxylic acid, methyl ester, propyl tiglate, propyl / isobutylcyclopent-3-enyl-1-acetate (alpha vinyl), butyl 2-furoate, ethyl 2-pentenoate, (E) -Methyl 3-pentenoate, 3-methoxy-3-methylbutyl acetate, n-pentyl crotonate, n-pentyl isobutyrate, propyl formate, furfuryl butyrate, methyl angelate, methyl pivalate, prenyl caproate, furfuryl propionate, diethyl maleate, isopropyl 2-methylbutyrate, dimethyl malonate, bornyl formate, styrallyl acetate, 1-(2-furyl)-1-propanone, l-citronellyl acetate, 3,7-dimethyl-1,Examples of the aryl esters include, but are not limited to, 6-nonadiene-3-yl acetate, neryl crotate, dihydromyrcenyl acetate, tetrahydromyrcenyl acetate, lavandulyl acetate, 4-cyclooctenyl isobutyrate, cyclopentyl isobutyrate, 3-methyl-3-butenyl acetate, allyl acetate, geranyl formate, cis-3-hexenyl caproate, and mixtures thereof.

[0029] Preferred alcohol fragrance materials include benzyl alcohol, beta-gamma-hexenol (2-hexen-1-ol), cedrol, citronellol, cinnamic alcohol, p-cresol, cumin alcohol, dihydromyrcenol, 3,7-dimethyl-1-octanol, dimethylbenzylcarbinol, eucalyptol, eugenol, fenchyl alcohol, geraniol, hydratoic alcohol, isononyl alcohol (3,5,5-trimethyl-1-hexanol), and linalool. , Methyl Chavicol (Estragole), Methyl Eugenol (Eugenyl Methyl Ether), Nerol, 2-Octanol, Patchouli Alcohol, Phenylhexanol (3-Methyl-5-phenyl-1-pentanol), Phenethyl Alcohol, Alpha-Terpineol, Tetrahydrolinalool, Tetrahydromyrcenol, 4-Methyl-3-decen-5-ol, 1-3,7-Dimethyloctan-1-ol, 2-(Furfuryl-2)-heptanol, 6,8-Dimethyl-2-nonanol, Ethyl 1,2-Dimethyl-2-(2-hexenyl)-1-ol, 3,7-dimethyl-(2)-6-octen(adiene)-1-ol, trans-2-undecen-1-ol, 2-ethyl-2-prenyl-3-hexenol, isobutylbenzylcarbinol, dimethylbenzylcarbinol, ocimenol, 3,7-dimethyl-1,6-nonadiene-3-ol (cis&trans), tetrahydromyrcenol, alpha-terpineol, 9-decenol-1,2-(2-hexenyl)-1-ol, cyclopentanol, 2,6-dimethyl-2-heptanol, 3-methyl-1-octen-3-ol, 379-trimethyl-1,6-decadien-3-ol, 3,7-dimethyl-6-nonen-1-ol, 3,7-dimethyl-1-octyne-3-ol, 2,6-dimethyl-1,5,7-octatrienol-3, dihydromyrcenol, 2,6-trimethyl-5,9-undecadienol, 2,5-dimethyl-2-propylhex-4-enol-1, (Z)-3-hexenol, o,m,Examples of suitable ethanolamines include, but are not limited to, p-methyl-phenylethanol, 2-methyl-5-phenyl-1-pentanol, 3-methylphenethyl alcohol, para-methyldimethylbenzyl carbinol, methylbenzyl carbinol, p-methylphenylethanol, 3,7-dimethyl-2-octen-1-ol, 2-methyl-6-methylene-7-octen-4-ol, and mixtures thereof.

[0030] Preferred ketone fragrance materials include oxacycloheptadec-10-en-2-one, benzylacetone, benzophenone, L-carvone, cis-jasmone, 4-(2,6,6-trimethyl-3-cyclohexen-1-yl)-but-3-en-4-one, ethyl amyl ketone, alpha-ionone, ionone beta, ethanone, octahydro-2,3,8,8-tetramethyl-2-acetonaphthalene, alpha -irone, 1-(5,5-dimethyl-1-cyclohexen-1-yl)-4-penten-1-one, 3-nonanone, ethylhexyl ketone, menthone, 4-methyl-acetophenone, gamma-methyl ionone, methyl pentyl ketone, methyl heptenone (6-methyl-5-hepten-2-one), methyl heptyl ketone, methyl hexyl ketone, delta mucenone, 2-octanone, 2-pentyl-3-methyl-2-cyclopentenone cyclopentenone, 2-heptylcyclopentanone, alpha-methylionone, 3-methyl-2-(trans-2-pentenyl)-cyclopentenone, octenylcyclopentanone, n-amylcyclopentenone, 6-hydroxy-3,7-dimethyloctanoic acid lactone, 2-hydroxy-2-cyclohexen-1-one, 3-methyl-4-phenyl-3-buten-2-one, 2-pentyl-2,5,5-trimethylcyclopentanone, 2-cyclopentylcyclopentanol-1,5-methylhexan-2-one, gamma-dodecalactone, delta-dodecalactone, gamma-nonalactone, delta-nonalactone, gamma-octalactone, delta-undecalactone, gamma-undecalactone, alpha damascone, beta damascone, gamma damascone, delta damascone, and mixtures thereof.

[0031] Preferred ether fragrance materials include, but are not limited to, diphenyl oxide, p-cresyl methyl ether, 4,6,6,7,8,8-hexamethyl-1,3,4,6,7,8-hexahydro-cyclopenta(G)-2-benzopyran, beta-naphthyl methyl ether, methyl isobutenyl tetrahydropyran, 5-acetyl-1,1,2,3,3,6-hexamethylindane (phantolide), 7-acetyl-1,1,3,4,4,6-hexamethyltetralin (tonalide), 2-phenylethyl-3-methylbut-2-enyl ether, ethyl geranyl ether, phenylethyl isopropyl ether, and mixtures thereof.

[0032] Preferred alkene fragrance materials include, but are not limited to, allo-ocimene, camphene, beta-caryophyllene, cadinene, diphenylmethane, d-limonene, limolene, beta-myrcene, para-cymene, 2-alpha-pinene, beta-pinene, alpha-terpinene, gamma-terpinene, terpineolene, 7-methyl-3-methylene-1,6-octadiene, and mixtures thereof.

[0033] Preferred nitrile fragrance materials include, but are not limited to, 3,7-dimethyl-6-octenenitrile, 3,7-dimethyl-2(3),6-nonadienenitrile, (2E,6Z)-2,6-nonadienenitrile, n-dodecanenitrile, and mixtures thereof.

[0034] Preferred Schiff base fragrance materials include, but are not limited to, citronellyl nitrile, nonanal / methyl anthranilate, N-octylidene-anthranilic acid methyl ester, hydroxycitronellal / methyl anthranilate, methoxyphenylpropanal / methyl anthranilate, ethyl p-aminobenzoate / hydroxycitronellal, citral / methyl anthranilate, 2,4-dimethylcyclohex-3-enecarbaldehyde methyl anthranilate, hydroxycitronellal-indole, and mixtures thereof.

[0035] As used herein, the term "flavor" refers to an ingredient of a formulation that can impart or modify the taste and smell of a product, e.g., toothpaste or food. Flavors are usually used to impart an overall pleasant taste and odor, or taste and odor profile, to a product, either to provide a simply enjoyable experience, as in foods, or to mask unpleasant tastes and odors, as in medicines. A flavor or flavoring material can be described in terms of its aroma intensity, detection threshold, and quality. A "flavor" can be composed of one or more ingredients, which can be single chemicals, referred to herein as "flavoring materials," or a mixture of different "flavoring materials." Flavoring materials can be created by synthetic processes or extracted from natural, especially plants, to create naturally occurring plant and animal oils and exudates, e.g., vanilla. The synthetic and naturally derived flavoring materials can then be blended into flavors by skilled perfumers for use in consumer products. Flavoring materials can be obtained from specialized flavor suppliers, known as flavor houses, as individual chemicals, natural blends, or as proprietary specialty blends whose complete composition is not disclosed.Individual flavor materials, including known natural blends, can be found by consulting journals commonly used by those skilled in the art, such as "Perfume and Flavourist" or "Journal of Essential Oil Research", or journals listed in reference books, such as S. Arctander Perfume and Flavor Chemicals, 1969, Montclair, New Jersey, USA, and more recently republished by Allured Publishing Corporation Illinois (1994), "Perfume and Flavour Materials of Natural Origin", S. Arctander, Ed., Elizabeth, NJ, 1960, and "Flavourings", E. Ziegler and H. Ziegler (ed.), Wiley-VCH Weinheim, 1998. It will be understood that flavors can be volatile or have volatile components that are detected by the nose, similar to fragrances. Thus, flavor materials can also be classified according to their physical properties, such as volatility and hydrophobicity, using the methods described above for fragrance materials. Flavor materials can also be described according to their Hansen Solubility Parameters, using the method described above for fragrance materials.

[0036] Sources of flavoring materials include essential oils, floral oils, absolutes, resins, resinoids, balsams, and tinctures. Preferred flavoring materials include anise oil, ethyl-2-methylbutyrate, vanillin, cis-3-heptenol, cis-3-hexenol, trans-2-heptenal, butyl valerate, 2,3-diethylpyrazine, methylcyclo-pentenolone, benzaldehyde, valerian oil, 3,4-dimeth-oxyphenol, amyl acetate, amyl cinnamate, y-butyryllactone, trimethylpyrazine, phenylacetic acid, isovaleraldehyde. , Ethyl maltol, Ethyl vanillin, Ethyl valerate, Ethyl butyrate, Cocoa extract, Coffee extract, Peppermint oil, Spearmint oil, Clove oil, Anethole, Cardamom oil, Wintergreen oil, Cinnamaldehyde, Ethyl 2-methylvalerate, g-Hexenyl lactone, 2,4-Decadienal, 2,4-Heptadienal, Methyl thiazole alcohol (4-Methyl-5-b-hydroxyethyl thiazole), 2-Methylbutanethiol, 4-Mercaptothiazole Mercapto-2-butanone, 3-mercapto-2-pentanone, 1-mercapto-2-propane, benzaldehyde, furfural, furfuryl alcohol, 2-mercaptopropionic acid, alkylpyrazine, methylpyrazine, 2-ethyl-3-methylpyrazine, tetramethylpyrazine, polysulfides, dipropyl disulfide, methylbenzyl disulfide, alkylthiophenes, 2,3-dimethylthiophene, 5-methylfurfural, acetylfuran, 2,4-deoxy-1,2-propanediol, 1-mercapto- ... Cadienal, Guacol, Phenylacetaldehyde, b-Decalactone, d-Limonene, Acetoin, Amyl Acetate, Maltol, Ethyl Butyrate, Levulinic Acid, Piperonal, Ethyl Acetate, n-Octanal, n-Pentanal, n-Hexanal, Diacetyl, Monosodium Glutamate, Monopotassium Glutamate, Sulfur-containing amino acids such as Cysteine, 2-Methylfuran-3-thiol, 2-Methyldihydrofuran-3-thiol, 2,5-dimethylfuran-3-thiol, tetramethylpyrazine, propylpropenyl disulfide, propylpropenyl trisulfide, diallyl disulfide, diallyl trisulfide, dipropenyl disulfide, dipropenyl trisulfide, 4-methyl-2-[(methylthio)-ethyl]-1,3-dithiolane, 4,5-dimethyl-2-(methylthiomethyl)-1,3-dithiolane, 4-methyl-2-(methylthiomethyl)-1,3-dithiolane, hop oil, citrus oil such as lemon, orange, lime, and grapefruit citrus oil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] The inventors of the present invention have discovered a method for preparing high solids protein colloidal dispersions of controlled particle size and low viscosity containing an active ingredient that allows for the formation of stable microcapsules upon drying. The resulting microcapsules are stable in liquid product formulations and under the conditions required to prepare such liquid product formulations (e.g., pasteurization conditions in the case of beverage formulations).

[0038] The present invention relates to a method for preparing biodegradable microcapsules, (a) forming a solution comprising one or more plant-derived proteins in a solvent system, the solvent system comprising miscible co-solvents, a first co-solvent increasing the solubility of the plant-derived proteins and a second co-solvent decreasing the solubility of the plant-derived proteins; (b) inducing the plant-derived protein in solution to undergo a sol-gel transition to form a plant-derived protein hydrogel; (c) subjecting the plant-derived protein hydrogel to a shear treatment to form a plant-derived protein hydrogel slurry; (d) dispersing an active ingredient in the plant-derived hydrogel slurry to form a composition; (e) drying the composition to form microcapsules.

[0039] Any suitable plant-derived protein can be used in the present invention.In a preferred method of the present invention, the plant-derived protein is obtained from broad bean, mung bean, pea, rice, potato, rapeseed, lentil, chickpea, sunflower seed, pumpkin seed, flax, chia, canola, lupin, alfalfa, moringa, wheat, corn zein or sorghum, and preferably the plant protein is selected from pea protein, potato protein, rapeseed protein, lentil protein, chickpea protein, broad bean protein, mung bean protein, sunflower seed protein, pumpkin seed protein, flax protein, chia protein, canola protein, lupin protein, alfalfa protein, moringa protein and / or rice protein.More preferably, the plant-derived protein is pea protein and / or potato protein.Such proteins are considered to be hypoallergenic proteins.

[0040] Suitable plant-derived proteins further include: Brassica: e.g., Brassica balearica: Mallorca cabbage, Brassica carinata: Abyssinian mustard or Abyssinian cabbage, Brassica elongata: elongated mustard, Brassica fruticulosa: Mediterranean cabbage, Brassica hilarionis: St. Hilarion's cabbage, Brassica juncea: Indian mustard, brown mustard and mustard greens, Sarepta mustard, Brassica napus: rapeseed, canola, rutabaga, Brassica narinosa: broadbeaked mustard, Brassica nigra: black mustard, Brassica oleracea: kale, cabbage, collard greens, broccoli, cauliflower, Chinese broccoli, Brussels sprouts, kohlrabi, Brassica perviridis: tender greens, mustard spinach, Brassica rapa (also known as B. campestris): Chinese cabbage, turnip, rapini, komatsuna, Brassica rupestris: brown mustard, Brassica tournefortii: Asian mustard Solanaceae: e.g. tomato, potato, eggplant, bell pepper and chilli pepper; Cereals: e.g., corn, rice, wheat, barley, sorghum, millet, oats, rye, triticale, fonio Quasi-cereals: such as amaranth (also called amaranth, red amaranth, prince-of-Wales-feather), breadfruit, buckwheat, chia, cockscomb (also called quail grass or soko), pitseed goosefoot, qaniwa, quinoa and wattleseed (also called acacia seed); Legumes such as Acacia alata (Winged Wattle), Acacia decipiens, Acacia saligna (commonly known by a variety of names including coojong, golden-leaved wattle, orange wattle, and blue-leafed wattle), Arachis hypogaea (peanut), Astragalus galegiformis, Cytisus laburnum (common laburnum, golden chain, or golden rain), Cytisus supinus, Dolichos lablab (commonly known as lablab-bean, bonavist bean / pea, dolichos bean, seim bean, or sorghum bean); bean, love love bean, Egyptian bean, Indian bean, bataw, and Australian pea), Ervum lens (lentil), Genista tinctoria (common names include dyer's whin, waxen woad, and waxen wood), Glycine max (soybean), Lathyrus clymenum (pea vine or lathyrus), Lathyrus odoratus (pea vine or lathyrus), Lathyrus sativus (pea vine or lathyrus), Lathyrus sylvestris (pea vine or lathyrus), Lotus tetragonolobus (asparagus-pea or winged pea), Lupinus albus (lupine), Lupinus angustifolius(lupine), Lupinus luteus(lupine), Lupinus polyphyllus(lupine), Medicago sativa(alfalfa), Phaseolus aureus(mungbean), Phaseolus coccineus(green bean), Phaseolusnanus (green beans), Phaseolus vulgaris (mung beans), Pisum sativum (peas), Trifolium hybridum (clover), Trifolium pretense (red clover), Vicia faba (broad beans), Vicia sativa (fava beans), Vigna unguiculate (cowpeas) Non-legumes: for example: Acanshosicyos horrida, Aesculus hyppocastanum, Anacardium occidentale, Balanites aegyptica, Bertholletia excels, Beta vulgaris, Brassica napus, Brassica juncea, Brassica nigra, Brassica hirta, Cannabis sativa, Citrullus vulgaris, Citrus aurantiaca, Cucurbita maxima, Fagopyrum esculentum, Gossypium barbadense (extra long staple cotton), Heianthus annuus (sunflower), Nicotiana sp. (tobacco), Prunus avium (cherries), Prunus spp. (sour cherries), Prusus domestica (plums), Prusus amygdalus (almonds), Rricinus communis (castor beans / castor oil plant), Sasamum indicum (sesame), Sinapis alba (white mustard), and Terlfalrea pedata (persimmon nuts).

[0041] For the avoidance of doubt, plant-derived microcapsules of the present invention do not encompass plants in their natural state, e.g. naturally formed plant cells, organelles or vesicles are not plant-derived microcapsules of the present invention.

[0042] In step (a), the first co-solvent increases the solubility of the plant-derived protein. The first co-solvent can be considered as a solubilizing co-solvent. There may be one or more solubilizing co-solvents, which can completely or partially solubilize the plant-derived protein. The co-solvent can be added in step (a) in a highly concentrated or diluted form.

[0043] An example of a solubilizing co-solvent is an organic acid. An organic acid is an organic compound that has acidic properties. Preferably, the organic acid is sourced from a natural plant-derived or bio-derived feedstock.

[0044] In a preferred method of the present invention, the first co-solvent is an organic acid. Preferably, the organic acid is acetic acid, lactic acid, formic acid, gluconic acid, propionic acid, α-hydroxy acid and / or β-hydroxy acid. Preferred α-hydroxy acids include glycolic acid, lactic acid, acetic acid, malic acid, citric acid and / or tartaric acid, preferably lactic acid or acetic acid. Preferred β-hydroxy acids include β-hydroxypropionic acid, β-hydroxybutyric acid, β-hydroxyβ-methylbutyric acid, 2-hydroxybenzoic acid and carnitine. In a particularly preferred method of the present invention, the organic acid is acetic acid and / or lactic acid.

[0045] The use of organic acid allows plant protein to be solubilized and also allows for gentle hydrolysis of protein.For example, without wishing to be bound by theory, the solubility of plant-derived protein in organic acid is possible due to i) protein protonation, and ii) the presence of an anion solvation layer that contributes to reducing hydrophobic interactions.When initially dissolved in organic acid, the protonation of plant-derived protein can help stabilize them in its non-solvent, for example, water.

[0046] In step (a), the second co-solvent reduces the solubility of the plant-derived protein compared to the first co-solvent. The second co-solvent may be considered a desolubilizing co-solvent. There may be one or more desolubilizing co-solvents.

[0047] In a preferred method of the present invention, the second co-solvent is selected from water, ethanol and / or ethyl acetate, more preferably water and / or ethanol, even more preferably water.

[0048] In a preferred method of the invention, in the solvent system, the cosolvent ratio of the first cosolvent to the second cosolvent is about 10-90% v / v, preferably about 20-90% v / v, preferably about 20-80% v / v, preferably about 20-60% v / v, about 25-55% v / v, about 30-50% v / v, about 20%, about 30%, about 40%, about 50% or about 60% v / v, most preferably about 30-50% v / v.

[0049] In a preferred method of the invention, the first co-solvent is present in the solution of step (a) at a concentration on a weight % basis that is greater than or equal to the concentration of the protein.

[0050] In a preferred method of the invention, the pH of the plant-derived protein solution in step (a) is at least 0.5 pH units, more preferably at least 1.0 pH units, lower than the isoelectric point of the plant-derived protein.

[0051] In a preferred method of the present invention, the concentration of the plant-derived protein in the solvent system is 25-200 mg / mL, more preferably 50-150 mg / mL.

[0052] The ratio of organic acids may vary depending on the protein concentration, for example, a higher organic acid ratio may be used with increasing protein concentration.

[0053] In a preferred method of the invention, the degree of protein hydrolysis (i.e., the percentage of broken peptide bonds in the protein hydrolysate) is controlled to modify the properties of the resulting hydrogel. For example, increasing the acid concentration present during formation increases the degree of protein hydrolysis. A higher degree of protein hydrolysis results in the formation of a less rigid hydrogel.

[0054] In a preferred method according to the invention the degree of protein hydrolysis is between 0.1 and 10%, preferably between 0.1 and 5%, even more preferably between 0.1 and 2.5%.

[0055] To form a solution containing one or more plant-derived proteins, it may be necessary to apply a physical stimulus to the protein / solvent system mixture to allow the proteins to dissolve. Suitable physical stimuli include heating, sonication, stirring, high shear mixing, high shear homogenization or other physical techniques. A preferred technique is heating, optionally followed by sonication.

[0056] Preferably, the protein / solvent system mixture is subjected to a physical stimulus which is heating, and the solution is heated to about 70° C. or greater. More preferably, the protein / solvent system mixture is heated to about 75° C. or greater, about 80° C. or greater, about 85° C. or greater, or about 90° C. Even more preferably, the protein / solvent system mixture is heated to 85° C.

[0057] Preferably, the protein / solvent system mixture is subjected to a physical stimulus of heating for about 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, or for a period of time greater than 30 minutes. The heated protein / solvent system mixture is optionally subjected to a subsequent ultrasonic treatment.

[0058] In a preferred method of the invention, in step (b), the protein solution is heated to a first temperature higher than the sol-gel transition temperature of the one or more plant-derived protein solutions and then reduced to a second temperature lower than the sol-gel transition temperature of the one or more plant-derived protein solutions to form a hydrogel.

[0059] The protein solution is heated so that the liquid solution is maintained above the sol-gel transition of the protein. By modifying the solvent system (e.g., through selection of the organic acid, the ratio of organic acid to additional solvent, or through additional means), it is possible to modify the sol-gel transition temperature of the protein. Through appropriate selection of conditions, it is possible to carefully control the sol-gel transition of the protein, and thereby control the formation of the hydrogel.

[0060] Preferably, the protein solution is heated to about 70° C. or greater. More preferably, the protein is heated to about 75° C. or greater, about 80° C. or greater, about 85° C. or greater, or about 90° C. Even more preferably, the protein is heated to 85° C.

[0061] The protein solution may be held at elevated temperature for about 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 45 minutes, or 1 hour. A preferred time is at least 30 minutes to allow complete solubilization of the protein. It is possible to hold the protein solution at elevated temperature for longer periods of time.

[0062] After heating the protein solution to a temperature above the sol-gel transition temperature, the temperature of the protein solution can be reduced to a second temperature below the sol-gel transition temperature to facilitate the formation of a hydrogel. The second temperature can be room temperature. The second temperature can be in the range of 5-25°C, preferably 10-20°C. The protein solution can be kept at the low temperature for an extended period of time, such as days or weeks, before carrying out the shearing treatment in step (c). The protein solution can be kept at the low temperature for about 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes or about 30 minutes. A particular shortened time is about 5 minutes.

[0063] The particular temperature will depend on the properties of the protein source, the solvent conditions used, and therefore the sol-gel transition temperature. Alternatively, the high and low temperatures may be relatively fixed (e.g., about 85° C., then about room temperature), with the co-solvent mixture conditions adjusted to ensure a suitable sol-gel transition temperature for the selected plant-derived protein.

[0064] Without wishing to be bound by theory, it is believed that when plant proteins are added to a solvent system, they form a dispersion of insoluble colloidal protein aggregates. Aggregate size can be measured by Dynamic Light Scattering (DLS). A suitable instrument for measuring aggregate size is the Zetasizer Nano S (Malvern).

[0065] It is believed that when a protein solution is heated above the sol-gel transition temperature in the presence of a co-solvent system, the plant protein is partially unfolded, exposing hydrophobic amino acids that were initially buried within the protein's native structure. Once partially unfolded, the co-solvent can interact with the unfolded protein molecule. For example, organic acids can not only favor protonating amino acid residues, but also form anionic salt bridges that stabilize hydrophobic interactions. Also, heating at high temperatures disrupts protein-protein non-covalent intermolecular contacts.

[0066] Furthermore, the application of mechanical agitation, e.g., ultrasonication, is believed to break down large colloidal protein aggregates into smaller aggregates and also disrupt protein intermolecular interactions.Using this approach, the size of protein aggregates can be significantly reduced to a particle size of less than 100 nm before gelation.Preferably, the above method includes protein aggregates with an average size of less than 200 nm, preferably less than 150 nm, less than 125 nm, less than 100 nm, less than 90 nm, less than 80 nm, less than 70 nm, less than 60 nm, less than 50 nm, less than 40 nm, or less than 30 nm.Therefore, at this stage of the method, the plant-derived protein is believed to have a protein secondary structure with a high level of α-helix and random coil.

[0067] Furthermore, cooling the protein solution below the sol-gel transition temperature is believed to allow protein-protein non-covalent intermolecular contacts and thus promote the self-assembly of interconnected protein aggregates of plant protein molecules into hydrogels.

[0068] After gelation, the aggregates may be fine strands. The aggregates may have a median average length of 50-500 nm. The aggregates may have an average length of 50-500 nm. 80% of the aggregates may have an average length of 50-500 nm. The aggregates may have a median height of 5-50 nm. The aggregates may have an average height of 5-50 nm. 80% of the aggregates may have an average height of 5-50 nm. In a preferred embodiment, the aggregates have a median average length of 50-500 nm and / or a median average height of 5-50 nm.

[0069] It is believed that the methods of the present invention allow plant proteins to aggregate into supramolecular structures through intermolecular hydrogen bonding interactions, in particular through interactions between β-strands.

[0070] The method of the present invention allows for the formation of materials in which there is a high level of β-sheet intermolecular interactions. Thus, in the method of the present invention, the plant derived protein has a protein secondary structure with at least 40% intermolecular β-sheets, at least 50% intermolecular β-sheets, at least 60% intermolecular β-sheets, at least 70% intermolecular β-sheets, at least 80% intermolecular β-sheets, or at least 90% intermolecular β-sheets, the % intermolecular β-sheet content being measured by FTIR (Fourier Transform Infrared Spectroscopy).

[0071] In a preferred method of the present invention, the plant-derived protein hydrogel is subjected to a solvent reduction step, preferably a solubilizing solvent reduction step, between step (b) and step (c).

[0072] By solubilizing solvent is meant a solvent or mixture of solvents in which the plant-derived protein hydrogel dissolves. Examples include organic acids such as acetic acid, lactic acid, formic acid, propionic acid, α-hydroxy acids and / or β-hydroxy acids. The α-hydroxy acids may preferably be selected from glycolic acid, acetic acid, lactic acid, malic acid, citric acid and / or tartaric acid. The β-hydroxy acids may preferably be selected from β-hydroxypropionic acid, β-hydroxybutyric acid, β-hydroxyβ-methylbutyric acid, 2-hydroxybenzoic acid and carnitine.

[0073] In a preferred method of the invention, the solvent reduction step comprises: (i) contacting a plant-derived protein hydrogel with a non-solubilizing solvent; (ii) separating the plant-derived hydrogel from the non-solubilizing solvent to obtain a washed plant-derived protein hydrogel; (iii) optionally repeating steps (i) and (ii).

[0074] Step (i) involves contacting the plant-derived protein hydrogel with a non-solubilizing solvent, by which is meant a solvent or mixture of solvents in which the plant-derived protein hydrogel does not dissolve. Examples include water or a mixture of water and ethanol.

[0075] In a preferred method of the present invention, the shear treatment comprises one step (i.e., a single shear step). The single shear step may be a higher shear step. Preferably, the single shear step involves fragmenting the plant-derived protein hydrogel into fragments.

[0076] In a preferred method of the invention, the fragments produced in a single shear step have a d of 0.5 to 50 microns, preferably 1 to 40 microns, preferably 2 to 30 microns, as measured by laser diffraction. 50 has.

[0077] In preferred methods of the invention, the single shear step involves sonication (e.g., using equipment such as a Bandelin HD4200 or Hielscher UIP1000hdT), high shear mechanical stirring (e.g., using equipment such as a Silverson rotor-stator high shear mixer), high pressure homogenization, or cavitation, preferably sonication.

[0078] In a preferred method of the invention, a single shear step is performed at a temperature below the sol-gel transition temperature of the plant-derived protein solution, In a preferred method of the invention, the first shear step is performed for at least 5 minutes, more preferably at least 1 minute.

[0079] In a preferred method of the present invention, the shearing treatment comprises two steps. Preferably, the shearing treatment comprises a first shearing step followed by a second shearing step. The first shearing step may be a low shearing step and the second shearing step may be a high shearing step.

[0080] In a preferred method of the invention, the first shearing step involves fragmenting the plant derived protein hydrogel into fragments. Preferably, at least 50% by weight of the fragments produced in the first shearing step have a particle size in the range of 1 mm to 100 mm, preferably 1 mm to 50 mm, preferably 5 mm to 30 mm, more preferably 10 mm to 30 mm. More preferably, at least 80% by weight of the fragments produced in the first shearing step have a particle size in the range of 1 mm to 100 mm, preferably 1 mm to 50 mm, preferably 5 mm to 30 mm, more preferably 10 mm to 30 mm. This can be measured by optical microscopy or visually.

[0081] In a preferred method of the present invention, the first shear step is carried out at a temperature below the sol-gel transition temperature of the plant derived protein solution.

[0082] In a preferred method of the invention, the first shearing step involves mechanical cutting, which means cutting with a knife edge (e.g. knife, extruder blade, etc.).

[0083] In an alternative preferred method of the invention, the first shearing step involves extrusion. For example, the plant-derived protein solution formed in step (a) can be extruded into a non-solubilizing solvent (e.g., water) to form the plant-derived protein hydrogel in large discrete fragments, e.g., the large discrete fragments can take the form of an extrudate having the form of threads or strings. In this way, the fragments can be directly subjected to a solvent reduction step, as described in more detail below. A first shearing step of this nature is more suitable for large-scale processing. In this case, the first shearing step can reduce at least one dimension of the large fragments, e.g., the diameter of the extrudate, to between 1 mm and 100 mm. Preferably, at least 50% by weight of the fragments produced in the first shearing step have at least one internal dimension in the range of between 1 mm and 100 mm, preferably between 1 mm and 50 mm, preferably between 5 mm and 30 mm, more preferably between 10 mm and 30 mm. More preferably, at least 80% by weight of the fragments produced in the first shearing step have an internal dimension in the range of 1 mm to 100 mm, preferably 1 mm to 50 mm, preferably 5 mm to 30 mm, more preferably 10 mm to 30 mm, which can be measured by optical microscopy or visually.

[0084] In a preferred method of the invention, the second shearing step involves further fragmenting the plant derived protein hydrogel. Preferably, the fragments produced in the second shearing step have a d of 0.5-50 microns, preferably 1-40 microns, preferably 2-30 microns, as measured by laser diffraction. 50 has.

[0085] In a preferred method of the present invention, the particle size distribution of the hydrogel fragments in the plant-derived protein hydrogel slurry can be adjusted by varying the nature and intensity of the second shear step. In another preferred method, the particle size distribution of the hydrogel fragments in the plant-derived protein hydrogel slurry can be adjusted by blending or combining two or more different hydrogel slurries that are subjected to different second shear steps and have different particle size distributions.

[0086] In a preferred method of the invention, the second shear step is carried out at a temperature below the sol-gel transition temperature of the plant derived protein.

[0087] In a preferred method of the invention, the second shear step is carried out at a temperature below the protein denaturation temperature of the plant-derived protein.

[0088] In a preferred method of the invention, the second shearing step is carried out for at least 5 minutes, more preferably at least 1 minute.

[0089] In preferred methods of the invention, the second shearing step involves sonication (e.g., using equipment such as a Bandelin HD4200 or Hielscher UIP1000hdT), high shear mechanical stirring (e.g., using equipment such as a Silverson rotor-stator high shear mixer), high pressure homogenization, or cavitation, preferably sonication.

[0090] In a preferred method of the present invention, step (c) further comprises subjecting the plant-derived protein hydrogel slurry to a solvent reduction step, preferably a solubilizing solvent reduction step, between said first shearing step and said second shearing step.

[0091] In a preferred method of the invention, the solvent reduction step comprises: (i) contacting the plant-derived hydrogel slurry fragments with a non-solubilizing solvent; (ii) separating the plant-derived hydrogel slurry fragments from the non-solubilizing solvent to obtain a washed plant-derived protein hydrogel; (iii) optionally repeating steps (i) and (ii).

[0092] The solubilizing solvent is as defined above.

[0093] Step (i) involves contacting the pieces of the plant-derived protein hydrogel slurry with a non-solubilizing solvent, which is as defined above.

[0094] In a preferred method of the invention, step (ii) involves mesh filtration or centrifugation, more preferably step (ii) involves mesh filtration using multiple size reducing meshes.

[0095] As will be appreciated by those skilled in the art, if the fragments produced in the first shearing step are too small, the solvent reduction step may be difficult because the fragments may eventually plug the mesh or the collection yield may be low. However, if the fragments produced in the first shearing step are too large, the solvent reduction step may take excessive time because of slow mass transfer of the solvent from the center of the fragments.

[0096] Without wishing to be bound by theory, it is believed that due to the porosity of the hydrogel, the solvent reduction step can remove some or all of the solvent (e.g., organic acid) from the hydrogel via solvent exchange.

[0097] The strength of the protein hydrogel can be altered by varying the concentrations of protein and organic acids, among other variables.

[0098] It is useful for the strength of the hydrogel used to form the hydrogel slurry to be within certain limits. This can be measured by oscillatory rheometry. A suitable measure of hydrogel strength is the storage modulus G' of the hydrogel. The suitable test conditions are 1% strain at 20°C with an oscillatory frequency of 1 Hz. A suitable instrument is an Anton Paar MCR 92 Rheometer with a cone and plate measurement geometry of 50 mm diameter and 1 degree angle.

[0099] Thus, in a preferred method of the invention, before washing, the plant derived protein hydrogel has a storage modulus (G') at 10 rad / s of greater than 1000 Pa, preferably greater than 2000 Pa, more preferably greater than 5000 Pa, even more preferably greater than 6000 Pa, and most preferably greater than 8000 Pa. As will be appreciated by those skilled in the art, 2π rad / s is equal to 1 Hz.

[0100] In a preferred method of the invention, before washing, the plant derived protein hydrogel has a storage modulus (G') at 10 rad / s of less than 20,000 Pa, preferably less than 15,000 Pa, more preferably less than 10,000 Pa.

[0101] In a preferred method of the present invention, before washing, the plant-derived protein hydrogel has a storage modulus (G') of about 1000 to 20,000 Pa, preferably about 2000 to 15,000 Pa, more preferably about 2000 to 10,000 Pa at 10 rad / s.

[0102] Furthermore, in a preferred method of the present invention, the washed plant derived protein hydrogel has a storage modulus (G') at 10 rad / s of greater than 200 Pa, preferably greater than 250 Pa, more preferably greater than 300 Pa, even more preferably greater than 350 Pa, more preferably greater than 400 Pa, more preferably greater than 450 Pa.

[0103] In a preferred method of the invention, the washed plant derived protein hydrogel has a storage modulus (G') at 10 rad / s of less than 5000 Pa, preferably less than 2500 Pa, preferably less than 1000 Pa, preferably less than 950 Pa, more preferably less than 900 Pa, more preferably less than 850 Pa, more preferably less than 800 Pa, more preferably less than 750 Pa.

[0104] In a preferred method of the present invention, the washed plant-derived protein hydrogel has a storage modulus (G') of about 200-5000 Pa, about 200-2500 Pa, about 200-1000 Pa, about 250-950 Pa, about 300-900 Pa, about 350-850 Pa, about 400-800 Pa, or about 450-750 Pa at 10 rad / s.

[0105] A preferred method of the present invention further comprises adding additional formulation ingredients to the plant-derived protein hydrogel slurry in step (c), preferably selected from plasticizers, surfactants, rheology modifiers, opacifiers, preservatives, pigments, carbohydrates, gums, polymers, and nanoparticles, or mixtures thereof.

[0106] In a preferred method of the invention, the additional formulation ingredient is a plasticizer, preferably selected from glycerol, ethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, sorbitol, mannitol, xylitol, fatty acids, glucose, mannose, fructose, sucrose, lactic acid, citric acid, glycolic acid, malic acid, gluconic acid, tartaric acid, ethanolamine, urea, triethanolamine, vegetable oils, lecithin, waxes and amino acids.

[0107] A preferred method of the present invention further comprises the step of altering the pH of the plant-derived protein hydrogel slurry so that it differs from the isoelectric point of the plant-derived protein by more than 1 pH unit.

[0108] Preferably, the step of changing the pH of the plant-derived protein hydrogel slurry is performed after step (c), or alternatively, the step of changing the pH of the plant-derived protein hydrogel slurry is performed consecutively with step (c).

[0109] During the adjustment of the pH of the plant-derived protein hydrogel slurry, the slurry may pass the isoelectric point of the protein. Due to the lack of charge repulsion at the isoelectric point, the dispersed protein fragments in the plant-derived protein hydrogel slurry may rapidly coagulate. To avoid this, the pH can be rapidly altered using a pH modifying material to minimize the time the slurry is at the isoelectric point. The isoelectric point of a particular plant-derived protein can be measured using the method described in Helmick et al., Food Biophysics (2021) 16: 474-483.

[0110] Therefore, in a preferred method of the present invention, the step of modifying the pH of the plant-derived protein hydrogel slurry involves adding a pH modifying material to the plant-derived protein hydrogel slurry. Preferably, the pH modifying material is a solution containing monovalent metal ions, divalent metal ions or ammonium ions, preferably an aqueous alkaline solution containing monovalent metal ions, divalent metal ions or ammonium ions. More preferably, the pH modifying material is an aqueous hydroxide solution, preferably sodium hydroxide, potassium hydroxide or ammonium hydroxide.

[0111] In a preferred method of the present invention, the pH of the plant-based protein hydrogel slurry after the step of altering the pH of the plant-based protein hydrogel slurry is at least 1 pH unit below the isoelectric point of the plant-derived protein.

[0112] In a preferred method of the present invention, the pH of the plant-based protein hydrogel slurry after the step of altering the pH of the plant-based protein hydrogel slurry is at least 1 pH unit higher than the isoelectric point of the plant-derived protein.

[0113] As will be appreciated by those skilled in the art, the addition of additional formulation ingredients to the plant-derived protein hydrogel slurry in step (c) may affect the pH of the slurry. Therefore, the step of modifying the pH of the plant-derived protein hydrogel slurry is preferably performed after the addition of any additional formulation ingredients.

[0114] In a preferred method of the present invention, the composition formed in step (d) is a shear thinning composition.

[0115] In a preferred method of the present invention, the composition formed in step (d) is heated at 20° C. and 50 s -1 Preferably, the viscosity is in the range of 1 to 10,000 cP at 20°C and 50s. -1 Viscosity in the range of 10 to 7500 cP at 20°C and 50 s -1 It has a viscosity in the range of 15 to 5000 cP.

[0116] In a preferred method of the invention, the composition formed in step (d) has a protein solids content in the range of 1% to 25%, preferably 2% to 20%, more preferably 4% to 15%, even more preferably 5% to 12% by weight based on the total weight of the composition. The term "protein solids" refers to the dry dispersed hydrogel solids derived from the plant protein added in step (a). Plant proteins are typically plant protein isolates that are primarily composed of material chemically identifiable as protein, but also contain low levels of other insoluble plant material such as fiber. The % protein solids is measured according to the methods described herein.

[0117] In a preferred method of the present invention, the active ingredient is selected from vitamins, minerals, flavor materials, fragrance materials, pro-flavors, pro-fragrances, flavor enhancers, malodor counteractants, nutritional supplements, live organisms (e.g., probiotics), pharmaceuticals, antibacterial agents, antiviral agents, anti-inflammatory agents, insecticides, herbicides, fertilizers, fungicides, insecticides, animal repellents, anti-acne agents, skin brighteners, skin emollients, skin moisturizers, wrinkle control agents, fabric softener actives, surface cleaning actives, skin conditioning agents, hair conditioning agents, dyes, pigments, and adhesives, or combinations thereof.

[0118] In a particularly preferred method of the invention, the active ingredient is at least one fragrance or flavor material, preferably selected from alcohols, aldehydes, ketones, esters, ethers, acetates, alkenes, nitriles, nitrogen heterocycles, sulfur heterocycles, and Schiff bases.

[0119] The fragrance and flavor materials used in the present invention may be of natural origin (i.e., they are extracted from natural sources and are not synthetically modified in any way).Preferred fragrance or flavor materials of natural origin include nutmeg extract, cardamom extract, ginger extract, cinnamon extract, patchouli oil, geranium oil, orange oil, mandarin oil, orange flower extract, cedarwood, vetiver, lavandin, ylang extract, tuberose extract, sandalwood oil, bergamot oil, rosemary oil, spearmint oil, peppermint oil, lemon oil, lavender oil, citronella oil, chamomile oil, clove oil, sage oil, neroli oil, labdanum oil, eucalyptus oil, verbena oil, mimosa extract, daffodil extract, jasmine extract, frankincense extract, rose extract, vanillin, coffee extract, hops oil, or combinations thereof.Preferably, the fragrance or flavor materials of natural origin are derived from plants. The naturally occurring fragrance or flavor materials may be used alone or in combination, or in combination with synthetic fragrance materials.

[0120] In a preferred method of the present invention, at least one fragrance or flavour material has a vapour pressure of 0.00001 Torr or greater at 25°C.

[0121] In a preferred method of the present invention, at least one fragrance or flavour material has a logP of 3.0 or greater, preferably 3.5 or greater, more preferably 4.0 or greater.

[0122] In a preferred method of the present invention, the at least one fragrance or flavor material has at least two Hansen solubility parameters selected from an atomic dispersion power (δD) of 14-20, a dipole moment (δP) of less than 8, and a hydrogen bond (δH) of 2.5-11.

[0123] In a preferred method of the invention, the at least one fragrance or flavour material is part of a fragrance or flavour.

[0124] Preferably, the fragrance or flavor contains at least 20% by weight, based on the total weight of the fragrance or flavor, of fragrance or flavor materials having a logP of 3.0 or greater, more preferably 3.5 or greater, more preferably 4.0 or greater.

[0125] Preferably, the fragrance or flavour contains at least 40% by weight, based on the total weight of the fragrance or flavour, of fragrance or flavour materials having a logP greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.0.

[0126] Preferably, the fragrance or flavour contains at least 50% by weight, based on the total weight of the fragrance or flavour, of fragrance or flavour materials having a logP greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.0.

[0127] Preferably, the fragrance or flavour contains at least 60% by weight, based on the total weight of the fragrance or flavour, of fragrance or flavour materials having a logP greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.0.

[0128] Preferably, the fragrance or flavour contains at least 10% by weight, preferably at least 30% by weight, more preferably at least 50% by weight, more preferably at least 70% by weight of fragrance or flavour materials of natural origin, based on the total weight of the fragrance or flavour.

[0129] Preferably, the fragrance or flavor contains at least 10% by weight of a fragrance or flavor material that has a biodegradation rate based on O2 consumption measured according to ISO-14851 version 2019 after 28 days of 60-100%, more preferably 65%, even more preferably 70-100%, even more preferably 75-100%, even more preferably 80-100%, even more preferably 85-100%, and most preferably 90-100%, based on the ratio of Biological Oxygen Demand (BOD) to theoretical oxygen demand. Since the fragrance or flavor has low water solubility, the fragrance or flavor can be added to a biodegradation test on an inert support according to ISO 10634 version 2018: Water quality-Preparation and treatment of poorly water-soluble organic compounds for the subsequent evaluation of their biodegradability in an aqueous medium. In addition, the fragrance or flavor can be checked for an inhibitory effect on microorganisms as detailed in the method.

[0130] Preferably, the fragrance or flavor contains at least 80% by weight, preferably at least 90% by weight, more preferably at least 95% by weight, of fragrance or flavor material having at least two Hansen solubility parameters selected from an atomic dispersion power (δD) of 14 to 20, a dipole moment (δP) of less than 8, and a hydrogen bond (δH) of 2.5 to 11, based on the total weight of the fragrance or flavor.

[0131] Preferably, the fragrance or flavor contains only low levels of materials with alcohol functionality (e.g., primary alcohol functionality). In a preferred method of the present invention, the fragrance or flavor contains less than 40% by weight, more preferably less than 20% by weight, of alcohol-containing materials, based on the total weight of the fragrance or flavor. In a particularly preferred method of the present invention, the fragrance or flavor does not contain any alcohol-containing materials. Without wishing to be bound by theory, it is believed that alcohols, especially primary alcohols with straight chain alkyl groups, can easily diffuse through the shell of the microcapsule due to their structure, which means that they can be difficult materials to encapsulate.

[0132] Preferably the fragrance or flavour material has a high odour impact, which is advantageous as it ensures that even low levels of fragrance are perceived when released from the microcapsules.

[0133] In an alternative particularly preferred method of the present invention, the active ingredient is a vitamin or mineral.Preferably, the active ingredient is a vitamin or mineral selected from vitamin A, vitamin B1, vitamin B2, vitamin B3, vitamin B5, vitamin B6, vitamin B7, vitamin B9, vitamin B12, vitamin C, vitamin D, vitamin E, vitamin K, magnesium, sodium, potassium, zinc, iron, calcium, iodine, linseed oil, omega-3 fatty acids, folic acid, thiamine, riboflavin, niacin and phosphorus, or mixtures thereof.More preferably, the active ingredient is vitamin D.

[0134] The vitamins and minerals used in the present invention may be provided from vitamin- and / or mineral-containing materials, an example of such a material being seaweed.

[0135] In an alternatively preferred method of the present invention, the active ingredient is an agrochemical, such as a pesticide, herbicide, fertilizer, fungicide, insecticide, animal repellent, or combinations thereof.

[0136] Preferably, the pesticide is a natural alternative to synthetic materials and is based on plant extracts and / or plant essential oils, or components of essential oils, such as thymol.Preferably, the pesticide is a biopesticide.Preferably, the pesticide is suitable for use in formulations for the management and production of plants that can be certified as organic by organizations such as the USDA (US Department of Agriculture) or Ecocert in Europe.

[0137] In a preferred method of the invention, the active ingredient is part of a composition comprising the active ingredient and an active carrier phase. Preferably, the active carrier phase is a solvent, a fat or a wax.

[0138] In a preferred method of the invention, the active carrier phase is a solvent. Preferably, the solvent is a solvent with low volatility (e.g., having a vapor pressure of less than 0.1 Torr at 25° C., preferably less than 0.01 Torr at 25° C., preferably less than 0.001 Torr at 25° C.).

[0139] Preferably, the solvent has low or no odor.

[0140] Preferably, the solvent has at least two Hansen solubility parameters selected from atomic dispersion forces (δD) less than 20, dipole moment (δP) less than 8, and hydrogen bonding (δH) less than 11. More preferably, the solvent has at least two Hansen solubility parameters selected from atomic dispersion forces (δD) less than 20, dipole moment (δP) less than 4, and hydrogen bonding (δH) less than 5.

[0141] Preferably, the solvent has a viscosity of 1.07 g / cm 3 A solvent with this property can advantageously prevent creaming of the encapsulate (e.g., in the final product formulation).

[0142] Preferably, the solvent contains only low levels of materials with alcohol functionality (e.g., primary alcohol functionality). In a preferred method of the invention, the solvent contains less than 40% by weight, more preferably less than 20% by weight, of alcohol-containing materials, based on the total weight of the solvent. In a particularly preferred method of the invention, the solvent is free of alcohol-containing materials.

[0143] In a preferred method of the invention, the active carrier phase is a solvent selected from carboxylic acid esters, fatty acid esters, phthalates, triols, diols, rosin resins, isoparaffins, terpenes, and vegetable oils, or combinations thereof.

[0144] Preferably, the solvent is Miglyol® 840, Miglyol® 812 N, Miglyol® 829, Miglyol® 829 ECO, Miglyol® Coco 810, Miglyol® 810 N, Miglyol® 128, Miglyol® 808, Miglyol® T-C7, Miglyol® 8810, Miglyol® PPG 810, Miglyol® OE, Miglyol® DO, and Miglyol® 818, Abalyn®, limonene, benzyl benzoate, diethyl phthalate, isopropyl myristate, triethyl citrate, dipropylene glycol, and propylene glycol, triacetin, glycerin, 1,3 propanediol, or combinations thereof, preferably Miglyol® 812 N.

[0145] Preferably, the solvent is a vegetable oil selected from coconut oil, corn oil, canola oil, cottonseed oil, olive oil, palm oil, peanut oil, rapeseed oil, safflower oil, sesame oil, soybean oil, and sunflower oil. Other examples of vegetable oils are described in CTFA Cosmetic Ingredient Handbook, JM Nikitakis (ed.), 1st ed., The Cosmetic, Toiletry and Fragrance Association, Inc., Washington, 1988. Vegetable oils are oils derived from plant sources. Alternatively, the solvent is derived from vegetable oils.

[0146] In a preferred method of the invention, the active carrier phase is a fat or wax having a melting point below 60°C, preferably below 45°C, preferably below 25°C.

[0147] Preferably, the wax is selected from Softisan® 100, Softisan® 142, and Softisan® 154, or combinations thereof, preferably Softisan® 100.

[0148] In the method of the present invention, the method used to form the composition in step (d) is not particularly limited.For example, step (d) can involve membrane emulsification, mechanical stirring (e.g., low or high shear mechanical stirring), ultrasonic treatment, high shear mechanical stirring, high pressure homogenization and / or cavitation.

[0149] In a preferred process of the invention, step (d) is carried out at a temperature in the range of 30°C to 50°C, preferably 35°C to 45°C.

[0150] In a preferred method of the invention, the composition formed in step (d) comprises droplets of the active ingredient or the composition comprises droplets of the active ingredient and a diameter of 0.5 to 50 microns, preferably 1 to 40 microns, preferably 2 to 30 microns, as measured by laser diffraction. 50 and an active carrier phase having

[0151] In a preferred method of the invention, in step (d) an additive, preferably a water-soluble additive, is added to the composition.

[0152] Preferably, the additive is selected from plasticizers, surfactants, rheology modifiers, opacifiers, preservatives, pigments, carbohydrates, gums, polymers, and nanoparticles, or mixtures thereof.

[0153] In a preferred method of the invention, the additive is a plasticizer, preferably selected from glycerol, ethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, sorbitol, mannitol, xylitol, fatty acids, glucose, mannose, fructose, sucrose, lactic acid, citric acid, glycolic acid, malic acid, gluconic acid, tartaric acid, ethanolamine, urea, triethanolamine, vegetable oils, lecithin, waxes and amino acids.

[0154] In a preferred method of the present invention, the additive is a polysaccharide, preferably maltodextrin or OSA starch. The use of a polysaccharide additive allows the composition of the matrix of the resulting microcapsule to be controlled. For example, the use of a polysaccharide means that the amount of plant-derived protein can be controlled.

[0155] In a preferred method of the invention, the water-soluble additive is a water-soluble vitamin, preferably vitamin C. The presence of an additive such as a water-soluble vitamin means that the final dry microcapsules are capable of delivering the additive in addition to the encapsulated active ingredient during end use, for example upon enzymatic degradation of the plant-derived protein hydrogel matrix in the oral cavity or digestive tract of a human or animal.

[0156] In a preferred method of the invention, the weight ratio of plant derived protein in the composition formed in step (d) to the composition comprising the active ingredient and the active carrier phase is in the range 20:1 to 1:20.

[0157] In a preferred process of the invention, the composition formed in step (d) is a homogenous composition.

[0158] In a preferred method of the invention, the composition formed in step (d) is a two-phase system (eg, an aqueous two-phase system).

[0159] In the method of the present invention, step (e) involves drying the composition formed in step (d) to form microcapsules or agglomerates of microcapsules or larger bodies. Those skilled in the art are familiar with drying techniques and will know how to select the necessary conditions to achieve dry microcapsules or larger bodies. Suitable drying techniques include spray drying, electrostatic spray drying, spray freeze drying, and spray vacuum drying, as used herein, where the slurry is sprayed into a chamber under reduced pressure, so that the solvent can be removed at a lower temperature, thus avoiding the problem of thermal decomposition. Advantageously, in the method of the present invention, step (e) can be carried out at a relatively low temperature (e.g., a temperature below 100°C) under spray conditions to form fine slurry droplets. This aids in the formation of small sized microcapsules and also prevents the loss or decomposition of any volatile or sensitive materials that are encapsulated.

[0160] Alternative or additional drying techniques that can be used independently or in combination with spray drying to evaporate the solvent from the composition of step (d) include fluidized bed drying, film drying, drum drying, belt drying, conduction drying, infrared drying, or combinations thereof. The composition of step (d) can be dispersed and at least partially dried by spray drying to form microcapsules, which are then further dried by a secondary process such as fluidized bed drying. The extended drying time typical of fluidized bed drying typically allows for the use of lower drying temperatures. Some designs of spray dryers incorporate this two-stage drying process as an integral part of their design. Some fluidized bed drying processes, which typically involve spraying or dispersing the composition of step (d) onto or into a fluidized bed of particles, e.g., encapsulates of already dried composition (d), are preferred when larger encapsulates are required. The composition can be sprayed onto or into the fluidized bed. Depending on the process conditions, the composition spray agglomerates and / or coats (and thus deposits on) the microcapsules passing through. An example of a fluidized bed coating and drying process is a Wurster type powder coater. A person skilled in the art can easily define the conditions to control the size of the encapsulates from a fluidized bed drying process.

[0161] Depending on the required form of the dried composition from step (e), other drying processes can be selected. Film drying, where the composition is cast as a thin film onto a heated belt or drum, can be used to form aesthetic shapes that include the dried composition (d). Belt drying, which can use conductive or infrared heating, can be used in combination with other drying techniques to complete the drying under controlled conditions.

[0162] During drying in step (e), the plant-derived protein hydrogel slurry forms a plant-derived protein carrier that encapsulates the active ingredient in the form of microcapsules. During drying in step (e), at least a portion of both the first and second cosolvents can evaporate to form microcapsules. This evaporation does not occur at the same rate for the two cosolvents, so during the process, the slurry is typically more concentrated in the least volatile cosolvent. The microcapsules formed during drying can still contain both the first and second cosolvents trapped within the dried microcapsules, and their ratio may be different from their starting ratio in the solution in step (a).

[0163] In a preferred method of the invention, the biodegradation rate based on O2 consumption of the plant-derived protein carrier measured according to ISO-14851 version 2019 after 28 days based on the percentage of biological oxygen demand (BOD) to theoretical oxygen demand is 60-100%, more preferably 65-10%, even more preferably 70-100%, even more preferably 75-100%, even more preferably 80-100%, even more preferably 85-100%, and most preferably 90-100%. ISO-14851 version 2019 describes a method to measure the biodegradation of materials in natural aqueous environments using biological oxygen demand in a closed respirometer. This is achieved by exposing the material under laboratory conditions in an aqueous standard test medium to an inoculum from unadapted activated sludge that has not been exposed beforehand. The measured value is calculated as a percentage of the theoretical oxygen demand calculated from the molecular formula. An internal standard of microcrystalline cellulose is also tested, and if its biodegradation % is greater than 60% at the end of the test, the test is valid.

[0164] In a preferred method of the invention, the biodegradation percentage based on O2 consumption of the microcapsules measured according to ISO-14851 version 2019 after 28 days based on the percentage of biological oxygen demand (BOD) to theoretical oxygen demand is 60-100%, more preferably 65-10%, even more preferably 70-100%, even more preferably 75-100%, even more preferably 80-100%, even more preferably 85-100%, and most preferably 90-100%. ISO-14851 version 2019 describes a method to measure the biodegradation of materials in natural aqueous environments using biological oxygen demand in a closed respirometer. This is achieved by exposing the material under laboratory conditions in an aqueous standard test medium to an inoculum from unadapted activated sludge that has not been exposed beforehand. The measured value is calculated as a percentage of the theoretical oxygen demand calculated from the molecular formula. An internal standard of microcrystalline cellulose is also tested and if its biodegradation % is greater than 60% at the end of the test, the test is valid.

[0165] In a preferred process of the invention, step (e) involves electrostatic spray drying.

[0166] In a preferred process of the invention, the plant-derived protein residues formed during step (e) but which are not incorporated into microcapsules are recycled, preferably added back to step (a).

[0167] In a preferred method of the invention, the microcapsules have a d of 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 10 μm or less, as measured by laser diffraction. 50 has.

[0168] In preferred methods of the invention, the microcapsules have a diameter, as measured by optical microscopy, of 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 10 μm or less.

[0169] A preferred method of the present invention further comprises subjecting the microcapsules to a post-treatment step. Preferably, the post-treatment step comprises a non-covalent cross-linking step, a covalent cross-linking step or a coating formation step.

[0170] In a preferred method of the present invention, the post-treatment step comprises a non-covalent cross-linking step. Preferably, the non-covalent cross-linking step comprises treating the microcapsules with a non-covalent cross-linking agent selected from sodium tripolyphosphate (NaTPP), sodium hexametaphosphate, and phenolic compounds (e.g., tannic acid, caffeic acid, etc.).

[0171] In a preferred method of the present invention, the post-treatment step comprises a covalent cross-linking step. Preferably, the covalent cross-linking step comprises treating the microcapsules with a covalent cross-linking agent selected from genipin, epoxy compounds, glyceraldehyde, glutaraldehyde, formaldehyde, glyoxal, dialdehyde starch, microbial transglutaminase, and PolyCup® cross-linking resin, or a combination thereof.

[0172] In a preferred method of the present invention, the post-treatment step comprises a coating formation step.

[0173] In a preferred method of the invention, the coating formation step comprises treating the microcapsules with a metal compound, preferably selected from a silver compound or a gold compound, preferably a silver compound.

[0174] In a preferred method of the invention, the coating formation step comprises subjecting the microcapsules to a complex coacervation process using a polysaccharide, preferably selected from xanthan gum, gellan gum, and chitosan, or a combination thereof.

[0175] In a preferred method of the invention, the coating forming step comprises treating the microcapsules with an aqueous mineral solution to form a mineral coating. Preferably, the aqueous mineral solution comprises an iron salt, a calcium salt, a phosphate salt, a carbonate salt, a titanium salt or a zinc salt, or a combination thereof.

[0176] As will be appreciated by those skilled in the art, it is possible for multiple post-treatment steps to be carried out, for example in a preferred method of the invention the microcapsules are subjected to a non-covalent cross-linking step (e.g. using NaTPP), followed by a coating formation step (e.g. using chitosan) and, optionally, a further non-covalent cross-linking step (e.g. using NaTPP).

[0177] A preferred method of the present invention further comprises adding a flow aid to the microcapsules after step (e). Preferably, the flow aid is fumed silica. The addition of the flow aid can avoid agglomeration of the newly formed microcapsules.

[0178] A preferred process of the invention comprises further drying the microcapsules after step (e). Preferably, the further drying is selected from fluidized bed drying and / or tray drying.

[0179] A preferred method of the present invention further comprises resuspending the microcapsules in an external phase, preferably an external aqueous phase, more preferably hard water or an acidic buffer solution.

[0180] A preferred method of the present invention further comprises sieving the microcapsules, for example for size classification.

[0181] The present invention also provides biodegradable microcapsules obtained or obtainable by the above process.

[0182] The present invention also provides a method for the preparation of a biodegradable microcapsule composition, the method comprising: (a) preparing biodegradable microcapsules according to the method described above; (b) suspending the biodegradable microcapsules in the external phase.

[0183] Preferably, the external phase is an external aqueous phase, preferably hard water or an acidic buffer solution.

[0184] A preferred method of the invention further comprises adding a suspending agent to the external phase.

[0185] Preferably, the suspending agent is selected from gum acacia, alginic acid, pectin, xanthan gum, gellan gum, carbomer, dextrin, gelatin, guar gum, hydrogenated vegetable oil category 1, aluminum magnesium silicate, maltodextrin, carboxymethylcellulose, polymethacrylates, polyvinylpyrrolidone, sodium alginate, starch, zein, water insoluble crosslinked polymers such as crosslinked cellulose, crosslinked starch, crosslinked CMC, crosslinked carboxymethyl starch, crosslinked polyacrylates, and crosslinked polyvinylpyrrolidone, and expanded clays such as bentonite and laponite.

[0186] The present invention also provides a biodegradable microcapsule composition obtained or obtainable by the above process.

[0187] The present invention also provides biodegradable microcapsules comprising an active ingredient and a plant-derived protein carrier comprising a plant-derived protein, the plant-derived protein carrier encapsulating the active ingredient, and the plant-derived protein having a solubility of less than 50% when measured at a protein concentration of 5% w / w in an aqueous solution at pH 7 and 25°C.

[0188] Protein solubility is measured using the following protocol: a known amount of dried microcapsules is added to an aqueous solution, which is then centrifuged to separate the soluble and insoluble fractions. After centrifugation, the liquid supernatant (i.e., the soluble fraction) is removed without collecting any of the solids that settle to the bottom (i.e., the insoluble fraction). The resulting supernatant is analyzed for nitrogen content. The protein content in the supernatant is then calculated based on the nitrogen content using a factor of 6.25. Protein solubility is defined as the amount of protein in the supernatant divided by the amount of protein in the total aqueous solution.

[0189] In preferred biodegradable microcapsules of the present invention, the plant-derived protein has a solubility of less than 30%, more preferably less than 10%, when measured at a protein concentration of 5% w / w in aqueous solution at pH 7 and 25°C.

[0190] In preferred biodegradable microcapsules of the invention, at least 25%, more preferably at least 40%, even more preferably at least 50%, and even more preferably at least 60% of the initially encapsulated active ingredient remains present within the microcapsules after 10 days of incubation in water at 20° C., as measured by high performance liquid chromatography (HPLC). In alternative preferred biodegradable microcapsules of the invention, at least 25%, more preferably at least 40%, even more preferably at least 50%, and even more preferably at least 60% of the initially encapsulated active ingredient remains present within the microcapsules after 10 days of incubation in water at 20° C., as measured by gas chromatography (GC).

[0191] More preferably, the water is acidified to have a pH of less than 4.0, more preferably less than 3.0, more preferably less than 2.0, more preferably less than 1.0. Thus, the biodegradable microcapsules of the present invention are insoluble in water and stable under strong acidic conditions. This is an advantage that the biodegradable microcapsules of the present invention can be used in a variety of applications where such harsh conditions are common. For example, the biodegradable microcapsules can be added to beverage formulations, which are generally acidic, to deliver active ingredients (e.g., vitamins or minerals) to the consumer. The acid stability of the biodegradable microcapsules of the present invention also means that once consumed, the microcapsules can withstand the harsh acidic conditions of the stomach, so that the active ingredients are not released until they enter the small intestine and can be better absorbed. Thus, the biodegradable microcapsules of the present invention can provide a sustained release of the encapsulated active ingredients. This is because the plant-derived protein hydrogel matrix acts as an enteric coating.

[0192] A preferred biodegradable microcapsule of the present invention is obtained from plant-derived proteins from broad beans, mung beans, peas, rice, potato, rapeseed, lentils, chickpeas, sunflower seeds, pumpkin seeds, flax, chia, canola, lupin, alfalfa, moringa, wheat, corn zein or sorghum, preferably the plant protein is selected from pea protein, potato protein, rapeseed protein, lentil protein, chickpea protein, broad bean protein, mung bean protein, sunflower seed protein, pumpkin seed protein, flax protein, chia protein, canola protein, lupin protein, alfalfa protein, moringa protein and / or rice protein. More preferably, the plant-derived protein is pea protein and / or potato protein. Such proteins are considered to be hypoallergenic proteins.

[0193] In a preferred biodegradable microcapsule of the present invention, the plant-derived protein is pretreated with an organic acid. Preferably, the organic acid is acetic acid, lactic acid, formic acid, propionic acid, α-hydroxy acid and / or β-hydroxy acid. Particularly preferably, the organic acid is acetic acid and / or lactic acid.

[0194] Preferred α-hydroxy acids include glycolic acid, lactic acid, acetic acid, malic acid, citric acid and / or tartaric acid, more preferably lactic acid or acetic acid. Preferred β-hydroxy acids include β-hydroxypropionic acid, β-hydroxybutyric acid, β-hydroxyβ-methylbutyric acid, 2-hydroxybenzoic acid and carnitine.

[0195] In preferred biodegradable microcapsules of the present invention, the active ingredient is selected from vitamins, minerals, flavor materials, fragrance materials, pro-flavors, pro-fragrances, flavor enhancers, malodor counteractants, nutritional supplements, live organisms (e.g., probiotics), pharmaceuticals, antibacterial agents, antiviral agents, anti-inflammatory agents, insecticides, herbicides, fertilizers, fungicides, insecticides, animal repellents, anti-acne agents, skin brighteners, skin emollients, skin moisturizers, wrinkle control agents, fabric softener actives, surface cleaning actives, skin conditioning agents, hair conditioning agents, dyes, pigments, and adhesives, or combinations thereof.

[0196] In particular in the biodegradable microcapsules of the present invention, the active ingredient is at least one fragrance or flavor material, preferably selected from alcohols, aldehydes, ketones, esters, ethers, acetates, alkenes, nitriles, nitrogen heterocycles, sulfur heterocycles, and Schiff bases.

[0197] The fragrance and flavor materials used in the present invention may be of natural origin (i.e., they are extracted from natural sources and are not synthetically modified in any way).Preferred fragrance or flavor materials of natural origin include nutmeg extract, cardamom extract, ginger extract, cinnamon extract, patchouli oil, geranium oil, orange oil, mandarin oil, orange flower extract, cedarwood, vetiver, lavandin, ylang extract, tuberose extract, sandalwood oil, bergamot oil, rosemary oil, spearmint oil, peppermint oil, lemon oil, lavender oil, citronella oil, chamomile oil, clove oil, sage oil, neroli oil, labdanum oil, eucalyptus oil, verbena oil, mimosa extract, daffodil extract, jasmine extract, frankincense extract, rose extract, vanillin, coffee extract, hops oil, or combinations thereof.Preferably, the fragrance or flavor materials of natural origin are derived from plants. The naturally occurring fragrance or flavor materials may be used alone or in combination, or in combination with synthetic fragrance materials.

[0198] In preferred biodegradable microcapsules of the present invention, at least one fragrance or flavour material has a vapour pressure of 0.00001 Torr or greater at 25°C.

[0199] In preferred biodegradable microcapsules of the present invention, at least one fragrance or flavour material has a logP of 3.0 or greater, preferably 3.5 or greater, more preferably 4.0 or greater.

[0200] In preferred biodegradable microcapsules of the present invention, at least one fragrance or flavor material has at least two Hansen solubility parameters selected from an atomic dispersion power (δD) of 14-20, a dipole moment (δP) of less than 8, and a hydrogen bond (δH) of 2.5-11.

[0201] In preferred biodegradable microcapsules of the present invention, at least one fragrance or flavour material is part of a fragrance or flavour.

[0202] Preferably, the fragrance or flavor contains at least 20% by weight, based on the total weight of the fragrance or flavor, of fragrance or flavor materials having a logP of 3.0 or greater, more preferably 3.5 or greater, more preferably 4.0 or greater.

[0203] Preferably, the fragrance or flavour contains at least 40% by weight, based on the total weight of the fragrance or flavour, of fragrance or flavour materials having a logP greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.0.

[0204] Preferably, the fragrance or flavour contains at least 50% by weight, based on the total weight of the fragrance or flavour, of fragrance or flavour materials having a logP greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.0.

[0205] Preferably, the fragrance or flavour contains at least 60% by weight, based on the total weight of the fragrance or flavour, of fragrance or flavour materials having a logP greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.0.

[0206] Preferably, the fragrance or flavour contains at least 10% by weight, preferably at least 30% by weight, more preferably at least 50% by weight, more preferably at least 70% by weight of fragrance or flavour materials of natural origin, based on the total weight of the fragrance or flavour.

[0207] Preferably, the fragrance or flavor contains at least 10% by weight of a fragrance or flavor material that has a biodegradation rate based on O2 consumption measured according to ISO-14851 version 2019 after 28 days of 60-100%, more preferably 65%, even more preferably 70-100%, even more preferably 75-100%, even more preferably 80-100%, even more preferably 85-100%, and most preferably 90-100%, based on the ratio of biological oxygen demand (BOD) to theoretical oxygen demand. Since the fragrance or flavor has low water solubility, the fragrance or flavor can be added to a biodegradation test on an inert support according to ISO 10634 version 2018: Water quality-Preparation and treatment of poorly water-soluble organic compounds for the subsequent evaluation of their biodegradability in an aqueous medium. In addition, the fragrance or flavor can be checked for an inhibitory effect on microorganisms as detailed in the method.

[0208] Preferably, the fragrance or flavor contains at least 80% by weight, preferably at least 90% by weight, more preferably at least 95% by weight, of fragrance or flavor material having at least two Hansen solubility parameters selected from an atomic dispersion power (δD) of 14 to 20, a dipole moment (δP) of less than 8, and a hydrogen bond (δH) of 2.5 to 11, based on the total weight of the fragrance or flavor.

[0209] Preferably, the fragrance or flavor contains only low levels of materials with alcohol functionality (e.g., primary alcohol functionality). In preferred biodegradable microcapsules of the present invention, the fragrance or flavor contains less than 40% by weight, more preferably less than 20% by weight, of alcohol-containing materials, based on the total weight of the fragrance or flavor. In particularly preferred biodegradable microcapsules of the present invention, the fragrance or flavor does not contain alcohol-containing materials.

[0210] Preferably the fragrance or flavour material has a high odour impact, which is advantageous as it ensures that even low levels of fragrance are perceived when released from the microcapsules.

[0211] In an alternative particularly preferred biodegradable microcapsule of the present invention, the active ingredient is a vitamin or mineral. Preferably, the active ingredient is a vitamin or mineral selected from vitamin A, vitamin B1, vitamin B2, vitamin B3, vitamin B5, vitamin B6, vitamin B7, vitamin B9, vitamin B12, vitamin C, vitamin D, vitamin E, vitamin K, magnesium, sodium, potassium, zinc, iron, calcium, iodine, linseed oil, omega-3 fatty acids, folic acid, thiamine, riboflavin, niacin and phosphorus, or mixtures thereof. More preferably, the active ingredient is vitamin D.

[0212] The vitamins and minerals used in the present invention may be provided from vitamin- and / or mineral-containing materials, an example of such a material being seaweed.

[0213] In preferred biodegradable microcapsules of the present invention, the active ingredient is part of a composition comprising the active ingredient and an active carrier phase. Preferably, the active carrier phase is a solvent, a fat or a wax.

[0214] In preferred biodegradable microcapsules of the present invention, the active carrier phase is a solvent. Preferably, the solvent is a solvent with low volatility (e.g., having a vapor pressure of less than 0.1 Torr at 25° C., preferably less than 0.01 Torr at 25° C., preferably less than 0.001 Torr at 25° C.).

[0215] Preferably, the solvent has low or no odor.

[0216] Preferably, the solvent has at least two Hansen solubility parameters selected from atomic dispersion forces (δD) less than 20, dipole moment (δP) less than 8, and hydrogen bonding (δH) less than 11. More preferably, the solvent has at least two Hansen solubility parameters selected from atomic dispersion forces (δD) less than 20, dipole moment (δP) less than 4, and hydrogen bonding (δH) less than 5.

[0217] Preferably, the solvent has a viscosity of 1.07 g / cm 3 A solvent with this property can advantageously prevent creaming of the encapsulate (e.g., in the final product formulation).

[0218] Preferably, the solvent contains only low levels of materials with alcohol functionality (e.g., primary alcohol functionality). In preferred biodegradable microcapsules of the invention, the solvent contains less than 40% by weight, more preferably less than 20% by weight, of alcohol-containing materials, based on the total weight of the solvent. In particularly preferred biodegradable microcapsules of the invention, the solvent is free of alcohol-containing materials.

[0219] In preferred biodegradable microcapsules of the present invention, the active carrier phase is a solvent selected from carboxylate esters, fatty acid esters, phthalate esters, triols, diols, rosin resins, isoparaffins, terpenes, and vegetable oils, or combinations thereof.

[0220] Preferably, the solvent is Miglyol® 840, Miglyol® 812 N, Miglyol® 829, Miglyol® 829 ECO, Miglyol® Coco 810, Miglyol® 810 N, Miglyol® 128, Miglyol® 808, Miglyol® T-C7, Miglyol® 8810, Miglyol® PPG 810, Miglyol® OE, Miglyol® DO, and Miglyol® 818, Abalyn®, limonene, benzyl benzoate, diethyl phthalate, isopropyl myristate, triethyl citrate, dipropylene glycol, and propylene glycol, triacetin, glycerin, 1,3 propanediol, or combinations thereof, preferably Miglyol® 812 N.

[0221] Preferably, the solvent is a vegetable oil selected from coconut oil, corn oil, canola oil, cottonseed oil, olive oil, palm oil, peanut oil, rapeseed oil, safflower oil, sesame oil, soybean oil, and sunflower oil. Other examples of vegetable oils are described in CTFA Cosmetic Ingredient Handbook, JM Nikitakis (ed.), 1 th ed., The Cosmetic, Toiletry and Fragrance Association, Inc., Washington, 1988. Alternatively, the solvent is derived from a vegetable oil.

[0222] In preferred biodegradable microcapsules of the present invention, the active carrier phase is a fat or wax having a melting point below 60°C, preferably below 45°C, preferably below 25°C.

[0223] Preferably, the wax is selected from Softisan® 100, Softisan® 142, and Softisan® 154, or combinations thereof, preferably Softisan® 100.

[0224] In preferred biodegradable microcapsules of the present invention, the plant-derived protein carrier further comprises an additive, preferably a water-soluble additive.

[0225] Preferably, the additive is selected from plasticizers, surfactants, rheology modifiers, opacifiers, preservatives, pigments, carbohydrates, gums, polymers, and nanoparticles, or mixtures thereof.

[0226] In a preferred biodegradable microcapsule of the present invention, the additive is a plasticizer, preferably selected from glycerol, ethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, sorbitol, mannitol, xylitol, fatty acids, glucose, mannose, fructose, sucrose, lactic acid, citric acid, glycolic acid, malic acid, gluconic acid, tartaric acid, ethanolamine, urea, triethanolamine, vegetable oils, lecithin, waxes and amino acids.

[0227] In the preferred biodegradable microcapsules of the present invention, the additive is a polysaccharide, preferably maltodextrin or OSA starch. The use of a polysaccharide additive allows the composition of the matrix of the resulting microcapsule to be controlled. For example, the use of a polysaccharide means that the amount of plant-derived protein can be controlled.

[0228] In preferred biodegradable microcapsules of the present invention, the water-soluble additive is a water-soluble vitamin, preferably vitamin C. The presence of an additive such as a water-soluble vitamin means that the final microcapsules are capable of delivering the additive in addition to the encapsulated active ingredient during end use, for example upon enzymatic degradation of the plant-derived protein hydrogel matrix in the oral cavity or digestive tract of a human or animal.

[0229] In preferred biodegradable microcapsules of the present invention, the microcapsules have a d of 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 10 μm or less, as measured by laser diffraction. 50 has.

[0230] In preferred biodegradable microcapsules of the present invention, the microcapsules have a diameter, as measured by optical microscopy, of 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 10 μm or less.

[0231] Thus, in the biodegradable microcapsules of the present invention, the plant-derived protein has a protein secondary structure having at least 40% intermolecular β-sheets, at least 50% intermolecular β-sheets, at least 60% intermolecular β-sheets, at least 70% intermolecular β-sheets, at least 80% intermolecular β-sheets, or at least 90% intermolecular β-sheets, where the % intermolecular β-sheet content is measured by FTIR.

[0232] Preferred biodegradable microcapsules of the present invention are free or substantially free of crosslinking agents.

[0233] In an alternative preferred biodegradable microcapsule of the present invention, the plant-derived protein carrier is non-covalently modified by a non-covalent cross-linking agent, preferably selected from sodium tripolyphosphate, sodium hexametaphosphate, and phenolic compounds (e.g., tannic acid, caffeic acid, etc.).

[0234] In an alternative preferred biodegradable microcapsule of the present invention, the plant-derived protein carrier is covalently modified with a covalent cross-linking agent. Preferably, the covalent cross-linking agent comprises treating the microcapsule with a covalent cross-linking agent selected from genipin, epoxy compounds, glyceraldehyde, glutaraldehyde, formaldehyde, glyoxal, dialdehyde starch, microbial transglutaminase, and PolyCup® cross-linking resin, or a combination thereof.

[0235] In preferred biodegradable microcapsules of the present invention, the plant derived protein carrier has a coating deposited thereon. Preferably, the coating is a metal coating, a coacervate coating or a mineral coating.

[0236] In preferred biodegradable microcapsules of the present invention, the metal coating is a silver coating or a gold coating, preferably a silver coating.

[0237] In preferred biodegradable microcapsules of the present invention, the coacervate coating is formed from a polysaccharide. Preferably, the polysaccharide is selected from xanthan gum, gellan gum, and chitosan, or a combination thereof.

[0238] In preferred biodegradable microcapsules of the present invention, the mineral coating is formed from an aqueous mineral solution, preferably comprising an iron salt, a calcium salt, a phosphate salt, a carbonate salt, a titanium salt or a zinc salt, or a combination thereof.

[0239] Preferred biodegradable microcapsules of the present invention have a coating deposited on a covalently or non-covalently modified plant-derived protein matrix. Preferred characteristics of the coating are as described above.

[0240] In particularly preferred biodegradable microcapsules of the present invention, the plant-derived protein is pea protein and the active ingredient is vitamin D.

[0241] In the preferred biodegradable microcapsules of the present invention, the biodegradation rate based on O2 consumption of the plant-derived protein carrier measured according to ISO-14851 version 2019 after 28 days based on the Biological Oxygen Demand (BOD) as a percentage of the theoretical oxygen demand is 60-100%, more preferably 65-100%, even more preferably 70-100%, even more preferably 75-100%, even more preferably 80-100%, even more preferably 85-100%, and most preferably 90-100%. ISO-14851 version 2019 describes a method to measure the biodegradability of materials in natural aqueous environments using biological oxygen demand in a closed respirometer. This is achieved by exposing the material under laboratory conditions in an aqueous standard test medium to an inoculum from unadapted activated sludge that has not been previously exposed. The measured value is calculated as a percentage of the theoretical oxygen demand calculated from the molecular formula. An internal standard of microcrystalline cellulose is also tested and if its % biodegradation is greater than 60% at the end of the test, the test is valid.

[0242] In the preferred biodegradable microcapsules of the present invention, the biodegradation rate based on the O2 consumption of the microcapsules measured according to ISO-14851 version 2019 after 28 days based on the biological oxygen demand (BOD) as a percentage of the theoretical oxygen demand is 60-100%, more preferably 65-100%, even more preferably 70-100%, even more preferably 75-100%, even more preferably 80-100%, even more preferably 85-100%, and most preferably 90-100%. ISO-14851 version 2019 describes a method to measure the biodegradability of materials in natural aqueous environments using biological oxygen demand in a closed respirometer. This is achieved by exposing the material under laboratory conditions in an aqueous standard test medium to an inoculum from a previously unexposed unadapted activated sludge. The measured value is calculated as a percentage of the theoretical oxygen demand calculated from the molecular formula. An internal standard of microcrystalline cellulose is also tested and if its % biodegradation is greater than 60% at the end of the test, the test is valid.

[0243] The present invention also provides a composition comprising the above-described biodegradable microcapsules and an external phase.

[0244] Preferably, the external phase is an external aqueous phase, preferably hard water or an acidic buffer solution.

[0245] Preferred compositions of the present invention further comprise a suspending agent in the external phase.

[0246] Preferably, the suspending agent is selected from gum acacia, alginic acid, pectin, xanthan gum, gellan gum, carbomer, dextrin, gelatin, guar gum, hydrogenated vegetable oil category 1, magnesium aluminum silicate, maltodextrin, carboxymethylcellulose, polymethacrylates, polyvinylpyrrolidone, sodium alginate, starch, zein, water insoluble crosslinked polymers such as crosslinked cellulose, crosslinked starch, crosslinked CMC, crosslinked carboxymethyl starch, crosslinked polyacrylates, and crosslinked polyvinylpyrrolidone, and expanded clays such as bentonite and laponite.

[0247] The present invention also provides a formulated product comprising the biodegradable microcapsules described above.

[0248] The present invention also provides (a) preparing biodegradable microcapsules according to the method described above; (b) mixing the biodegradable microcapsules with a product formulation.

[0249] Preferably, the formulated product is a food, beverage, cosmetic, home care product, personal care product, pharmaceutical, industrial product (eg, paint, adhesive, sandpaper, tape, etc.), medical device, biomaterial, or pesticide.

[0250] The present invention also provides the use of the biodegradable microcapsules described above in formulated products.

[0251] Preferably, the formulated product is a food, beverage, cosmetic, home care product, personal care product, pharmaceutical, industrial product (eg, paint, adhesive, sandpaper, tape, etc.), medical device, biomaterial, or pesticide.

[0252] The formulated products described in the various aspects of the present invention may be in any form suitable for use. Preferably, the formulated products are in the form of a vapor spray, aerosol, emulsion, lotion, liquid, cream, gel, stick, ointment, paste, mousse, powder, granular product, matrix, or semi-solid. [Brief description of the drawings]

[0253] [Figure 1a] 10X optical microscope photographs of the microcapsules of Examples 2B and 2E, respectively. [Figure 1b] 10X optical microscope photographs of the microcapsules of Examples 2B and 2E, respectively. [Figure 2a] 10x optical microscope photographs of the microcapsules of Examples 4A and 4B, respectively. [Figure 2b] 10x optical microscope photographs of the microcapsules of Examples 4A and 4B, respectively. [Diagram 3] 10x optical microscope image of Example 5 control in water. [Figure 4a] 6A and 6B are SEM images of the microcapsules of Example 6A at magnifications of ×80 and ×300, respectively. [Figure 4b] 6A and 6B are SEM images of the microcapsules of Example 6A at magnifications of ×80 and ×300, respectively. [Figure 5a] 6A-6C are SEM images of the microcapsules of Example 6B at magnifications of ×60, ×500, and ×1250, respectively. [Figure 5b] 6A-6C are SEM images of the microcapsules of Example 6B at magnifications of ×60, ×500, and ×1250, respectively. [Figure 5c] 6A-6C are SEM images of the microcapsules of Example 6B at magnifications of ×60, ×500, and ×1250, respectively. [Figure 6] FIG. 1 is a SEM image of the microcapsules of Example 7 at ×1200 magnification. [Figure 7a] 7A and 7B are 10x optical microscope images of the microcapsules of Example 7 before (FIG. 7a) and after (FIG. 7b) they were pressed to release the oil. [Figure 7b] 7A and 7B are 10x optical microscope images of the microcapsules of Example 7 before (FIG. 7a) and after (FIG. 7b) they were pressed to release the oil. [Figure 8a] 10X microscope images of concentrated slurries of Examples 10A, 10B, and Comparative Example 10C. [Figure 8b] 10X microscope images of concentrated slurries of Examples 10A, 10B, and Comparative Example 10C. [Figure 8c] 10X microscope images of concentrated slurries of Examples 10A, 10B and Comparative Example 10C. [Figure 9] FIG. 10× light microscope of microcapsules of Example 15 in 1× citrate buffer. [Figure 10]Photograph of four inverted tubes of Example 16. EXAMPLES

[0254] material Pea Protein Isolate (PPI) (80% protein, 4% carbohydrate by weight - ProEarth P16109) was purchased from Cambridge Commodities Ltd.

[0255] Lactic acid (85%, food grade) was purchased from Fisher Scientific.

[0256] Acetic acid (glacial acetic acid 99%) was purchased from Fisher Scientific.

[0257] Sodium benzoate was purchased from Fisher Scientific.

[0258] Vitamin D2 oil (1 MIU / g) was purchased from Prinova Europe, UK.

[0259] Miglyol® 812N was purchased from IOI Oleochemical.

[0260] Softisan® 100 was purchased from IOI Oleochemical.

[0261] Vitamin D2 powder, VITAMIN D2 (ERGOCALCIFEROL) 100,000 IU / G SD, acacia gum system, was obtained from Prinova Europe, UK.

[0262] Robinsons Double Strength No Added SuSquash Apple & Blackcurrant (manufactured by Britvic Plc and commercially available from supermarkets in the UK).

[0263] Miwadi Single Concentrate Black Currant (manufactured by Britvic Plc and commercially available from supermarkets in the Republic of Ireland).

[0264] Thymol was purchased from Fisher Scientific, UK.

[0265] Calcium sulfate dihydrate (CaSO4·2H2O) was purchased from Fisher Scientific.

[0266] Dried magnesium sulfate (MgSO4) was purchased from Fisher Scientific.

[0267] Potassium chloride Extra Pure, SLR, Eur. Ph., (KCl) was purchased from Fisher Scientific.

[0268] Sodium bicarbonate (NaHCO3), certified by AR for analytical use, was purchased from Fisher Scientific.

[0269] Potassium hydroxide (KOH) (>85%) was purchased from Sigma Aldrich.

[0270] Absolute ethanol 99.8+% (EtOH), certified by AR for analytical grade, was purchased from Fisher Scientific.

[0271] Maltodextrin was purchased from Sigma-Aldrich Gillingham, UK.

[0272] Polysorbate 80 was purchased from Sigma-Aldrich Gillingham, UK.

[0273] All components of phosphate buffered saline (PBS) (pH 7.4) were purchased from Fisher Scientific, UK and prepared in the following proportions: NaCl 138 mM, KCl 2.7 mM, Na2HPO4 10 mM, NaH2PO4 2 mM.

[0274] Sodium acetate trihydrate was purchased from Alfar Aesar, UK.

[0275] Calcium chloride dihydrate was purchased from Fisher Scientific, UK.

[0276] Methylparaben was purchased from Alfar Aesar, UK.

[0277] Tannic acid was purchased from Fisher Scientific, UK.

[0278] Gellan gum (high acyl) was purchased from Special Ingredients Ltd, UK.

[0279] Linseed oil was purchased from Naissance, UK.

[0280] Fragrance Materials [Table 1]

[0281] Standard hard water and buffer compositions 1) Hard water It was prepared in deionized (DI) water with the following salt concentrations: 192 mg / L NaHCO3, 120 mg / L CaSO4·2H2O, 120 mg / L MgSO4, and 8 mg / L KCl. The pH was adjusted to 3 with 1 M HCl.

[0282] 2) 1x buffer solution 100 mL of 1x buffer solution was prepared as follows: i. Weighed out 1.904 g citric acid monohydrate and 0.276 g trisodium citrate dihydrate. ii. The mixture was made up to 80 g with deionized water. iii. Adjust the pH of the solution to 3 using 1M HCl and 1M NaOH solutions and bring the volume of the solution to 100 g with DI water; iv. 0.38 g of CaCl2 dihydrate is added; v.0.2 g of sodium benzoate was added, vi. Place the solution in an ultrasonic bath at 80°C for 5-10 minutes (i.e. until complete dissolution is observed); vii. The solution was allowed to cool to 20°C.

[0283] 3) 2x strength buffer 100 mL of 2x buffer was prepared similarly to the 1x buffer, except the levels of all ingredients were doubled and the mixture still finished at 80 g.

[0284] Measurement method Vitamin D2 assay for dry powder samples in microcapsules: Version A Vitamin D2 is extracted from the samples into dimethylsulfoxide and then partitioned into hexane. Vitamin D2 is quantified using normal phase HPLC with UV detection. This method is suitable for measuring high levels of vitamin D2, typically 35 iu / g to 500,000 iu / g.

[0285] Vitamin D2 Assay for Dry Powder Samples of Microcapsules: Version B The powdered sample (approximately 0.1 g) is suspended in 4 g of 50% w / v aqueous potassium hydroxide solution and 8 g of absolute ethanol. 0.1 g of sodium ascorbate is added. The sample is placed in an ultrasonic bath without heating for 1-1.5 h, cooled on ice, and then centrifuged at 14,500 rpm for 10 min prior to HPLC analysis on a reversed-phase column using 100% methanol as the eluent and UV detection at 265 nm.

[0286] Vitamin D2 assay for dilute liquid systems containing microcapsules The sample is cold saponified overnight in alcoholic potassium hydroxide (containing pyrogallol). The unsaponified fraction is separated by extraction into hexane. The extracted sample is then concentrated and injected into a semi-preparative HPLC column. The fraction of the eluent containing vitamin D2 is collected, evaporated to dryness, dissolved in methanol, and vitamin D2 is separated using reversed-phase HPLC with UV detection. This method is suitable for the measurement of low levels of vitamin D2, typically between 0.5 iu / g and 100 iu / g. Lower levels can be quantified with further dilution.

[0287] Hydrogel Slurry Particle Size The particle size of the hydrogel slurries was measured using an Anton Paar laser diffraction particle size analyzer PSA 1190. Measurements were performed by diluting the hydrogel within one hour of completion of preparation in an aqueous solution containing acetic or lactic acid adjusted to the same pH. The test material was diluted to the required concentration to ensure that no aggregates were present and that it had the desired optical density for the measurements (usually 5-15% obscuration). Quoted 50 is for the volume distribution calculated by a general analysis using Mie theory.

[0288] Droplet Size of Composition for Spray Drying The droplet size of the oil or wax containing the active ingredient in the composition used for spray drying was measured using an Anton Paar laser diffraction particle size analyzer PSA 1190. The measurements were carried out by diluting the composition within one hour after the end of production in an aqueous solution containing acetic or lactic acid adjusted to the same pH. The test material was diluted to the required concentration to have the desired optical density for the measurement (usually 5-15% obscuration). Quoted 50 is for the volume distribution calculated by a general analysis using Mie theory.

[0289] Protein Solids The solids content of the hydrogel slurry was measured by the mass remaining upon drying. Approximately 5 g of the hydrogel slurry was pipetted into a small polypropylene dish and the mass was accurately recorded. The dish was placed in a 40° C. oven overnight to dry. The dry mass was measured immediately after removing the dish from the oven and the solids content of the protein hydrogel slurry was calculated as a percentage of the initial wet mass.

[0290] Viscosity of the composition for spray drying The viscosity of the compositions for spray drying was measured within 1 hour of the end of the preparation of the compositions using an Anton Paar MCR 92 rheometer. The rheometer was set using a cone (1 degree, diameter 50 mm) and plate geometry. The viscosity was measured at a temperature of 20° C. and a shear rate of 50 / s.

[0291] Particle size of spray-dried microcapsules The particle size of the final microcapsule powder was measured using an Anton Paar laser diffraction particle size analyzer PSA 1190. The powder was added to reverse osmosis water diluted to the required concentration to obtain the desired optical density for the measurement (usually 5-15% obscuration). The dispersion should be checked under an optical microscope for any larger agglomerates of microcapsules. If these are visible, 0.5 wt% acetic acid can be added to ensure that the primary particles are well dispersed. Quoted 50 is for the volume distribution calculated by a general analysis using Mie theory.

[0292] Alternatively, particle size can be measured using an optical microscope (e.g., using an open frame microscope equipped with a CellCam 200CR camera, an Aura Pro phase contrast illuminator, and 4x, 10x, and 20x Universal Plan fluor objectives). Microcapsule powder is added to either reverse osmosis water or 1x buffer, as appropriate. In this method, particle size is obtained from the average size measurement of 50 microcapsules for each sample. The optical microscope is then calibrated using a grid from a Hirschmann hemocytometer (Fuchs Rosenthal). Using the line tool in ImageJ 1.53, particle size is measured from two center-edges with the overlay text function enabled to avoid capsule overlap.

[0293] Scanning Electron Microscope (SEM) SEM images were obtained using a Hitachi TM3030.

[0294] optical microscopy Optical microscopy was performed using an open frame microscope equipped with a CellCam 200CR camera, an Aura Pro phase contrast illuminator, and 4x, 10x, and 20x Universal Plan fluor objectives. Prior to microscopic imaging, samples were prepared for optical microscopy by first rehydrating the dried microcapsules in hard water or 1x buffer for 5 minutes. A cover slip was then placed on the rehydrated sample and an image was taken. The slide was then removed from the microscope stage and firm pressure was applied to the cover slip by hand before the sample was returned to the stage and an image of the broken capsules was taken.

[0295] Total Fragrance and Fragrance Ingredient Loading Fragrance and fragrance material levels in the spray dried microcapsules can be measured by extraction of the fragrance material and injection onto a GC column. Quantification is achieved by using a calibration curve for a given fragrance material diluted in ethanol.

[0296] To measure the total level of fragrance material in an encapsulated sample, the capsules must first be broken by sonication. For example, 10-50 mg of dry encapsulates or 0.3-0.5 g of wet encapsulates collected on a 40 μm cell strainer in 3.0 g of deionized (DI) water and 10% KOH are vortexed to thoroughly mix. The solution is then sonicated for 1-2 minutes at 30% amplitude (approximately 1.5-3.0 kJ total) using a Bandelin miniature probe TS104. Ice is used during sonication to keep the temperature below 20°C to avoid loss of fragrance through evaporation. Visually check if the capsules are completely broken using the optical microscope detailed above. If not, repeat the sonication step. Ethanol is added to the mixture, which is then mixed and centrifuged. The supernatant is collected and then appropriately diluted and injected into a GC for analysis.

[0297] For samples containing benzyl salicylate, this is quantified by measuring the benzyl alcohol formed from its hydrolysis.

[0298] Total thymol load Thymol levels in the spray dried microcapsules were determined by extracting thymol and injecting it onto a GC column according to the Total Fragrance Loading method herein.

[0299] Olfactory evaluation of microcapsule slurries For any given encapsulation, the total fragrance level is quantified by GC as described herein. Based on the encapsulation load, the material is diluted to deliver the appropriate level of fragrance for olfactory evaluation. Optionally, preservatives and suspending agents are added to the diluted encapsulation samples.

[0300] Using a low-shear micropipette tip, pipette 50 µL of diluted encapsulates onto a standard microscope glass slide, ensuring that most of the surface area is covered, leaving a clean edge for handling the slide. Repeat this at least four times.

[0301] 50 μL of the diluted encapsulate slurry is also pipetted onto a rectangular fragrance evaluation card blotter (approximately 9 cm×5 cm). This is repeated at least twice.

[0302] The slides and blotters were evaluated by trained evaluators at different time points. 1) Immediately after application, 2) Leave it overnight at 20-25℃ to dry, then 3) Leave the slide to dry overnight at 20-25°C, then rub the slide with a gloved index finger for 10 strokes (in either direction). 4) After leaving it to dry overnight at 20 to 25°C, the slide glass was pressed against another slide glass for 10 seconds and then removed.

[0303] 3) After leaving it to dry overnight at 20-25°C, the blotter paper was rubbed with another clean blotter paper for 10 strokes (in either direction).

[0304] Evaluators rated the intensity according to the following scale and commented on the fragrance characteristics:

[0305] [Table 2]

[0306] Example 1 - Preparation of Protein Hydrogel Slurry with Acetic Acid Preparation of protein hydrogels A 800 mL mixture was prepared consisting of 12.5% ​​(w / v) pea protein isolate (PPI) in 30% (v / v) acetic acid solution.

[0307] The mixture was then heated in a water bath at 85° C., followed by a sonication step to break up large colloidal aggregates (Hielscher UIP), after which a clear solution was obtained. The applied energy was 200 kJ.

[0308] The solution was then poured into a container to a depth of 1 cm and left to cool at 5° C. for 28 hours to obtain a free-standing protein hydrogel.

[0309] Application of shear to protein hydrogels Shear was then applied to the hydrogel as follows: The protein hydrogel was cut into cubes of approximately 1 cm by a low shear cutting process. The cubes were placed inside a 75 micron filter bag, which was then submerged in a bucket containing 10 L of reverse osmosis water. This formed a coarse protein hydrogel slurry inside the filter bag. The hydrogel cubes were allowed to soak with occasional gentle stirring. This process was performed to reduce the concentration of acetic acid in the hydrogel by diffusion into the continuous water phase.

[0310] The distorted gel cubes were transferred to a bottle containing 4 wt % sodium benzoate and exposed to high shear on ice followed by ultra-high shear (probe sonication up to 200 kJ using a Hielscher sonicator) to form a homogenous low viscosity protein hydrogel slurry.

[0311] Example 2 - Preparation of spray-dried microcapsules containing Vitamin D2 Preparation of wax / vitamin D2 mixture Mixtures of 22% (220,000 IU / g) and 11% (110,000 IU / g) by weight were made from Vitamin D2 oil (1 MIU / g) in Softisan® 100 wax. The wax was melted above 40° C., the vitamin oil was added, and the mixture was homogenized by shaking by hand. The mixture was kept above 40° C. until needed.

[0312] Example 2A: Acid-treated hydrogel slurry solids to wax at a ratio of 5 to 1 with Vitamin D2 added by sonication 1500 g of protein hydrogel slurry was made according to Example 1, the mixture of PPI and acetic acid was heated for 20 minutes, the gel cubes were soaked for 2 hours, then high sheared at 15,000 rpm for 15 minutes, and then ultra high sheared at 0.25 kj / mL to form a hydrogel slurry.

[0313] Preparation of the Composition The protein hydrogel slurry was heated to 35° C. and 22% by weight of the wax / vitamin D2 molten mixture was added, resulting in a protein hydrogel slurry to wax / vitamin D2 weight ratio of 98.3 to 1.7. The resulting mixture was mechanically high sheared using an Ultra-Turrax disperser at 15000 rpm for 10 minutes, followed by ultra-high shearing on ice using a Hielscher sonicator applying an energy of 0.1 kJ / mL. This resulted in a viscosity of 27.3 cP and an average droplet size d of 0.67 microns. 50 A composition having the following formula was obtained.

[0314] Spray drying of the composition The composition was spray dried according to the process settings in Table 1 and had a mean particle size d of 23.8 microns as measured by laser diffraction. 50 The vitamin D2 concentration in the microcapsule powder was measured using method version A described herein and found to be 100,250ug / 100g.

[0315] Example 2B: Acid-treated hydrogel slurry solids to wax in a 2 to 1 ratio with Vitamin D2 added by mechanical mixing 1500 g of protein hydrogel was made according to Example 1, the mixture of PPI and acetic acid was heated for 20 minutes, the gel cubes were soaked for 2 hours, then high sheared at 15,000 rpm for 15 minutes, and then ultra high sheared at 0.25 kj / mL to form a hydrogel slurry.

[0316] Preparation of the Composition The protein hydrogel was heated to 35° C. and 11% by weight of the wax / vitamin D2 molten mixture was added, resulting in a protein hydrogel slurry to wax / vitamin D2 ratio of 96 to 4 by weight. The resulting mixture was mechanically high sheared using an Ultra-Turrax disperser at 15,000 rpm for 10 minutes, which resulted in a viscosity of 31.4 cP and an average droplet size d of 4.6 microns. 50 A composition having the following formula was obtained.

[0317] Spray drying of the composition The slurry was spray dried according to the process settings in Table 1 to produce a mean particle size d of 35.9 microns measured by laser diffraction. 50 The vitamin D2 concentration in the microcapsule powder was measured using method version A described herein and found to be 94,750ug / 100g.

[0318] Example 2C: Acid-treated hydrogel slurry solids to wax at a ratio of 5 to 1 with Vitamin D2 added by mechanical mixing 1500 g of protein hydrogel slurry was made according to Example 1, the mixture of PPI and acetic acid was heated for 20 minutes, the gel cubes were soaked for 2 hours, then high sheared at 15,000 rpm for 15 minutes, and then ultra high sheared at 0.25 kj / mL to form a hydrogel slurry.

[0319] Preparation of the Composition The protein hydrogel slurry was heated to 35° C. and 22% by weight of the wax / vitamin D2 molten mixture was added, resulting in a protein hydrogel slurry to wax / vitamin D2 weight ratio of 96 to 4. The mixture was mechanically high sheared using an Ultra-Turrax disperser at 15,000 rpm for 10 minutes, which resulted in a viscosity of 35.8 cP and an average droplet size d of 6.2 microns. 50 A composition having the following formula was obtained.

[0320] Spray drying of the composition The composition was spray dried according to the process settings in Table 1. Two different settings were used to obtain samples Ci and Cii. The Ci and Cii microcapsules each had an average particle size d of 31.3 microns as measured by laser diffraction. 50 The Vitamin D2 concentration in the microcapsule powder was measured using method version A described herein and found to be 95,500ug / 100g.

[0321] Control Example 2D: 5 to 1 ratio of protein solids to wax in sonicated PPI (in 5 wt % acetic acid) with Vitamin D2 added by mechanical mixing. Preparation of PPI mixture A mixture of 8 wt% pea protein isolate in 5 wt% (v / v) acetic acid solution was prepared such that the solids concentration was comparable to the protein hydrogel slurry prepared in Example 1. The mixture was ultra-high sheared using a Hielscher probe sonicator with an energy input of 1 kJ / mL. This resulted in a mean particle size d 50 A protein mixture with a pH of 2.9 microns was obtained. The pH of the reaction mixture was adjusted to 3.4.

[0322] Preparation of the Composition The protein mixture was heated to 35° C. and 22% by weight of the wax / vitamin D2 molten mixture was added, resulting in a weight ratio of 98.3 to 1.7 protein mixture to wax / vitamin D2. The mixture was mechanically high sheared using an Ultra-Turrax disperser at 15,000 rpm for 10 minutes. This resulted in a viscosity of 5.0 cP and an average droplet size d of 4.4 microns. 50 A composition having the following formula was obtained.

[0323] Spray drying of the composition The composition was spray dried according to the process settings in Table 1 and had an average particle size d of 20.2 microns as measured by laser diffraction. 50The vitamin D2 concentration in the microcapsule powder was measured using method version A described herein and found to be 86,500ug / 100g.

[0324] Control Example 2E: 5:1 ratio of protein solids to wax in sonicated PPI with Vitamin D added by mechanical mixing. Preparation of PPI mixture A slurry of 8 wt% pea protein isolate in reverse osmosis water was prepared such that the solids concentration was comparable to the protein hydrogel slurry prepared in Example 1. The mixture was ultra-high sheared using a Hielscher probe sonicator with an energy input of 1 kJ / mL. This resulted in a mean particle size d 50 A protein mixture with a pH of 1.4 microns was obtained. The pH of the reaction mixture was adjusted to 6.85.

[0325] Preparation of the Composition The protein mixture was heated to 35° C. and 22% by weight of the wax / vitamin D2 molten mixture was added, resulting in a weight ratio of 98.3 to 1.7 protein mixture to wax / vitamin D2. The mixture was mechanically high sheared using an Ultra-Turrax disperser at 15,000 rpm for 10 minutes. This resulted in a viscosity of 4.9 cP and an average droplet size d of 4.6 microns. 50 A composition having the following formula was obtained.

[0326] Spray drying of the composition The composition was spray dried according to the process settings in Table 1 and had a mean particle size d of 40.0 microns as measured by laser diffraction. 50 The vitamin D2 concentration in the microcapsule powder was measured using method version A described herein and found to be 93,000ug / 100g.

[0327] Spray drying conditions for Examples 2A to 2E All compositions prepared in Examples 2A-2E were spray dried in a co-current spray dryer equipped with a 1 m diameter chamber and a Spraying Systems FloMax nozzle. The inlet air flow was maintained at 1.5 kg / min and the slurry feed addition rate was adjusted within the specified range to maintain the outlet temperature. The feed characteristics and spray drying conditions are summarized in Table 1 below.

[0328] [Table 3]

[0329] The conditions in Table 1 demonstrate that despite the higher feed viscosities of Inventive Examples 2A, 2B, and 2C compared to Controls 2D and 2E, the compositions were successfully spray dried at standard equipment and process conditions, which is believed to be due to the shear thinning properties of the compositions of Inventive Examples 2A, 2B, and 2C.

[0330] All compositions were successfully spray dried to produce particles with average particle size d of 20-40 microns as measured by laser diffraction. 50 1a and 1b are 10x optical micrographs of the spray dried microcapsules of Examples 2B and 2E, respectively, showing the visual similarity of the microcapsule powders produced. To achieve this, a much higher level of energy was used in preparing the protein dispersion of Example 2E than that of Example 2B to achieve similar emulsion droplet and microcapsule sizes.

[0331] Example 3 - Preparation of Protein Hydrogel Slurry with Lactic Acid Preparation of protein hydrogels 50.0 g of pea protein isolate was added to 212.5 g of reverse osmosis water in a bottle. The bottle was shaken to disperse the protein and 187.5 mL of 85% (v / v) lactic acid was mixed in. The mixture was placed in a water bath at 85° C. for 30 minutes and then sonicated with a Bandelin sonicator until 100 kJ was delivered. The protein solution was poured into a Petri dish and cooled at 5° C. overnight to obtain a free-standing protein hydrogel.

[0332] Application of shear to protein hydrogels The hydrogel was cut into 1 cm cubes and placed in a 75 micron nylon mesh bag in a bucket. 5 L of reverse osmosis water was added and the cubes were allowed to soak for approximately 1.5 hours with occasional gentle agitation. The water was then drained from the bag and the same soaking procedure was repeated three more times until the pH was above 3.0.

[0333] The hydrogel was then drained and added to a 5 wt% sodium benzoate solution at 20 mL per kilo of gel (pH was adjusted to 4-5 using lactic acid). The mixture was sonicated using a Bandelin sonicator until 0.1 kJ / mL was applied. The solids content of the hydrogel slurry was determined to be 5.1 wt% by the method described herein.

[0334] Example 4 - Preparation of spray-dried microcapsules containing Vitamin D2 Preparation of the Composition Vitamin D2 oil (1 MIU / g) was diluted with Miglyol® 812N or Softisan® 100 wax to a concentration of 6000 ug / g. This concentration was chosen to produce spray-dried particles containing a vitamin D2 concentration of 1,000 ug / g. In the case of Softisan® 100 wax, the wax was melted above 40° C., the vitamin oil was added, and the mixture was homogenized by shaking manually. The mixture was kept above 40° C. until needed.

[0335] The required mass of oil or wax and Vitamin D2 mixture was then added to the protein hydrogel slurry made in Example 3 to achieve a mass ratio of hydrogel slurry solids to Vitamin D2:wax / oil mixture of 5 to 1. The composition was formed by mixing with an IKA Ultra-Turrax at 5000 rpm for 15 minutes, followed by probe sonication to 0.1 kJ / mL with a Bandelin sonicator.

[0336] Spray drying conditions The experiments were carried out using a ProCept spray dryer in its three-column setup. The column height was 1.8 m and the column diameter was 0.15 m. A two-fluid nozzle with a 0.8 mm tip size was used. The atomization air flow rate was 10 mL / mL. Fluids were pumped into the spray dryer at 6 mL / min using a syringe pump. Other settings are shown in Table 2 below. The cyclone was set with an additional air flow rate of 100 L / min.

[0337] [Table 4]

[0338] The results demonstrate that protein hydrogel slurries formed using lactic acid can be spray dried under standard conditions using standard equipment. The results also demonstrate that a range of different carrier materials (e.g., oils and waxes) for the active ingredient, here vitamin D2, can be used.

[0339] In the spray drying experiments, the average particle size d measured by laser diffraction 50However, two free-flowing powders were produced, with 15.8 microns for Example 4A and 32.5 microns for Example 4B. The vitamin D2 concentration in the microcapsule powders was measured using method version A described herein and found to be 89,000 μg / 100 g and 86,500 μg / 100 g for Samples 4A and 4B, respectively. Figures 2a and 2b are optical micrographs at 10x of the spray dried microcapsules of Examples 4A and 4B, respectively, showing the visual similarity of the powders produced, with the difference in particle size being observable.

[0340] Example 5 - Accelerated stability study of Vitamin D2 microcapsules in a beverage formulation Sample preparation The microcapsules of Examples 4A and 4B were each added to Robinsons Double Concentrate No Added Sugar Apple & Blackcurrant squash. More specifically, 45 mg of microcapsules were added to 1 liter of squash to achieve a vitamin D concentration of 4.5 ug / 100 mL in the product, assuming a vitamin D concentration of 100,000 ug / 100 g in the microcapsules. A control was also prepared by adding 9 mg of Prinova spray-dried vitamin D2 to the same sample of squash. Prinova spray-dried vitamin D2 is a commercially available powdered vitamin D2 material. The three mixtures were heated to 95°C on a hot plate with constant stirring and then held at 95°C for 30 seconds to mimic the temperature profile during flash pasteurization. The mixtures were then cooled to 20°C.

[0341] Accelerated Stability Testing Each of the three squash samples was filled into a 200 mL clear plastic PET bottle and placed in a Binder KBF P 240-230V chamber, which was set for accelerated ambient light stability testing with UV-A set at 1.1 W / m2 at 20° C. and laboratory (typically 50% relative humidity (RH)). The initial Vitamin D2 loading in the squash was measured using the methods described herein and then measured again after 4 weeks in the binder chamber. The % decrease in Vitamin D2 content over the 4 week period was calculated and recorded in Table 3. Vitamin D2 is expected to degrade significantly when exposed to UV over this time frame.

[0342] [Table 5]

[0343] As can be seen from Table 3, after 4 weeks in the squash, the commercially available powdered vitamin D2 was almost completely degraded, with 95% of the initial vitamin D2 being degraded.

[0344] Figure 3 is a 10x microscope image of powdered control vitamin D2 added to cold tap water, showing the presence of a fine dispersion of material, with no microcapsules present. Without wishing to be bound by theory, it is believed that the carrier material in this powder is highly soluble in water and therefore disintegrates in water, and therefore is unable to protect the vitamin D2 in the accelerated stability test.

[0345] However, for Example 4A, after 4 weeks in squash, vitamin D2 level is still approximately half of the original level, demonstrating that this microcapsule with plant-derived protein carrier and oil-based active carrier phase protects vitamin D2 from UV exposure, thus reducing degradation. The presence of insoluble plant-derived protein carrier clearly helps protect encapsulated vitamin D2 compared to the commercial material tested in the control experiment. Furthermore, for Example 4B, after 4 weeks in squash, vitamin D2 level is substantially unchanged from the original level, demonstrating that this microcapsule with plant-derived protein carrier and wax-based active carrier phase can completely protect vitamin D2 from degradation. Without wishing to be bound by theory, it is believed that the use of a solid wax carrier for vitamin D2 means that the material surrounding the vitamin is more opaque, thus providing better protection of the vitamin from UV.

[0346] Example 6 - Preparation of spray-dried fragrance microcapsules Preparation of fragrance / solvent mixtures An 80:20 weight mixture of delta-damascone and Miglyol® 812 was prepared by gentle mixing.

[0347] Preparation of spray-dried microcapsules Protein hydrogel slurry was made according to Example 1, a mixture of PPI and acetic acid was heated for 30 minutes, gel cubes were soaked for 1 hour, then high sheared using an IKA Ultra-Turrax at 25,000 rpm for 15 minutes, then ultra high sheared using sonication (Hielscher sonicator) at 1.0 kj / mL to form a hydrogel slurry.

[0348] Average particle size of hydrogel slurry d 50was measured according to the methods described herein and found to be 2.5 microns. The average solids content of the hydrogel slurry was measured according to the methods described herein and found to be 8.6% by weight.

[0349] Two samples were prepared with the compositions shown in Table 4 by pouring the fragrance / solvent mixture into the hydrogel slurry and mixing with an Ultra-Turrax at 15,000 rpm for 5-15 seconds to achieve the desired dispersion droplet size of 5 μm.

[0350] [Table 6]

[0351] The Example 6A phase separated easily to give a clear liquid upper layer and a lower layer of hydrogel fragments, which could be rehomogenized by vigorous mixing prior to spray drying. The well-mixed slurry had a viscosity of 150 cP at 50 s−1.

[0352] A 1.5 mg droplet of Example 6A was suspended on a thin wire connected to a microbalance and placed in the center of a pipe with an inner diameter of 2.5 cm. Air at a temperature of 97° C. and a speed of 0.85 m / s was passed around the droplet and the weight of the droplet was recorded over a period of 11 minutes. At the end of the experiment, the dried droplet was carefully separated from the wire and placed on a Hitachi TM3030 SEM mounting pad for examination.

[0353] The resulting particles had an internal matrix structure and an external smooth skin, as can be seen in the SEM images of Figures 4a and 4b.

[0354] Example 6B was a homogenous, viscous semi-solid with a viscosity of 1000 cP at 50 / sec.

[0355] A 2.5 mg droplet of Example 6B was suspended on a thin wire connected to a microbalance and placed in the center of a pipe with an inner diameter of 2.5 cm. Air at a temperature of 85° C. and a speed of 0.85 m / s was passed around the droplet and the weight of the droplet was recorded for 3.5 minutes. At the end of the experiment, the dried droplet was carefully separated from the wire and placed on a Hitachi TM3030 SEM mounting pad for examination.

[0356] The resulting particles had a matrix structure and a porous surface, as can be seen in the SEM images of Figures 5a, 5b, and 5c.

[0357] Example 7 - Preparation of spray-dried fragrance microcapsules Preparation of fragrance / solvent mixtures An 80:20 volume ratio mixture of delta-damascone and Miglyol® 812 was prepared by gentle mixing.

[0358] Preparation of spray-dried microcapsules Protein hydrogel slurry was made according to Example 1. The hydrogel slurry was diluted with acetic acid to an average protein solids content of 8.0% by weight. A 221 g batch was mixed at 8000 rpm for 2 minutes using an UltraTurrax lab mixer. Then, 131 g of fragrance was added, an oil mixture containing 80% delta-damascone and 20% Miglyol® 812 oil. The composition is shown in Table 5 below.

[0359] [Table 7]

[0360] The batch was subjected to high shear for 5 minutes using an UltraTurrax lab mixer set at 8000 rpm to create a fine emulsion, with an expected droplet size of approximately 5 microns.

[0361] The samples were then spray dried using a ProCepT R&D Spray Dryer in its three column setup. The column height was 1.8 m and the column diameter was 0.15 m. The air inlet temperature was 130° C. with a flow rate of 550 L / min. A two-fluid nozzle with a 1.0 mm tip size was used. The atomization air flow rate was 10 L / min. The fluids were pumped into the spray dryer at 6 mL / min using a syringe pump. An additional air flow rate of 140 L / min was introduced below the drying chamber to carry the air to the cyclone.

[0362] The dry microcapsule powder formed from Example 7 was collected from the cyclone and also from the interior surfaces of the equipment where the dry microcapsule powder adhered, for example, in the transfer pipe to the cyclone.

[0363] The microcapsules of Example 7 were examined under a Hitachi TM3030 SEM and showed mostly spherical fragrance encapsulations with diameters of about 30 μm or less (FIG. 6). The microcapsules appeared to have uneven surfaces, indicating that there was very little free fragrance and that the sample was adequately dried.

[0364] The microcapsules of Example 7 were rehydrated in hard water and photographed under an optical microscope (Figure 7a). The same capsules were then compressed to break, releasing the oil therein (Figure 7b). The oil droplets are clearly visible around the broken microcapsules, and there is a very clear dark interface between the oil and the water.

[0365] The microcapsules of Example 7 were analyzed for their total fragrance loading by the methods described herein, which was found to be 28.8%.

[0366] Example 8 - Preparation of Protein Hydrogel Slurry with Acetic Acid Preparation of protein hydrogels 1120g of reverse osmosis (RO) water was added to a 2 litre stainless steel vessel and 216g of pea protein isolate was added. The vessel was placed in a 92°C water bath and mixed at 1500 rpm using an overhead stirrer. After stirring for 3 minutes, 480g of glacial acetic acid was added. The mixture was stirred at 1500 rpm for 15 minutes and then at 1200 rpm for 30 minutes, allowing the temperature of the mixture to exceed 85°C for at least 10 minutes. The mixture was poured into a tray to a depth of approximately 10mm and left at room temperature overnight.

[0367] Application of shear to protein hydrogels The hydrogel was then sheared as follows: The protein hydrogel was cut into approximately 1 cm cubes by a low shear cutting process. The cubes were divided between two 75 micron filter bags and then each was submerged in a bucket containing 16 L of RO water. This formed a coarse protein hydrogel slurry in the filter bag. The hydrogel cubes were soaked for 90-150 minutes while being stirred with an overhead stirrer at 600-800 rpm. This step was performed to reduce the concentration of acetic acid in the hydrogel by diffusion into the continuous water phase. The pH of the wash water was then measured and if it was above 3.2, soaking was continued for another 30 minutes. If it was below 2.9, half of the water was drained and replaced with fresh RO water and soaking was then continued for another 30 minutes. The filter bags were then hung over a bucket to drain for 5 minutes. The washed gel from both filter bags was transferred to a 5 liter beaker and homogenized using a Silverson mixer at 5000 rpm for 5 minutes, 6000 rpm for 5 minutes, and 7000 rpm for 5 minutes. The smooth slurry was then transferred to 1 L Nalgene bottles (800 g each) and exposed to high shear sonication (Hielscher UP500Hdt) with shaking every 75 kJ until 250 kJ was applied while cooling on ice. The hydrogel slurry was then passed through a 200 micron sieve before use.

[0368] Comparative Example 9 - Preparation of Acid-Free Protein Slurry 450g of reverse osmosis water was added to a 1L stainless steel vessel and 50g of pea protein isolate was added. The vessel was placed in a 92°C water bath and mixed at 1500 rpm with an overhead stirrer. The mixture was stirred at 1500 rpm for 15 minutes and then at 1200 rpm for 30 minutes, allowing the temperature of the mixture to exceed 85°C for at least 10 minutes. The mixture was cooled to ambient temperature and, in contrast to the experiment with acetic acid, no gel was formed. It was then sheared at 8000 rpm for 10 minutes with a Silverson mixer and then with a sonicator (Hielscher UP500Hdt) until 156 kJ was applied. For comparison, 0.3125 kJ / g was used for the protein slurry prepared with organic acids. The mixture was then passed through a 200 micron sieve before use.

[0369] Example 10 - Preparation of spray-dried microcapsules containing Vitamin D2 Preparation of the Composition Vitamin D2 oil (1 MIU / g) was diluted with Softisan® 100 wax to a concentration of 6000 ug / g. This concentration was chosen to produce spray-dried particles containing a vitamin D2 concentration of 1,000 ug / g. The wax was melted above 40° C., the vitamin oil was added, and the mixture was homogenized by shaking manually. The mixture was kept above 40° C. until needed.

[0370] The required mass of the wax and vitamin D2 mixture was then added to the protein hydrogel slurry of Example 8 and mixed with a Silverson L5M-A homogenizer at 7000 rpm for 10 minutes to form a composition containing vitamin D2 and wax with 11.9% total solids by weight. The composition was then further diluted with 3.0% aqueous acetic acid to produce two samples: Example 10A with 10.0% total solids (8.9% protein solids by weight) containing vitamin D2 and wax and Example 10B with 5.0% total solids (4.4% protein solids by weight) containing vitamin D2 and wax.

[0371] The required mass of wax and vitamin D2 mixture was also added to the protein slurry of Comparative Example 9 and mixed with a Silverson L5M-A homogenizer at 7000 rpm for 10 minutes to form a composition, which was then further diluted with 3.0% aqueous acetic acid to produce Comparative Example 10C having 11.7% total solids by weight (10% protein solids by weight) including vitamin D2 and wax.

[0372] Spray drying conditions For Examples 10A and 10B, spray drying was carried out using a ProCept spray dryer in its three-column configuration, with a column height of 1.8 m and a column diameter of 0.15 m.

[0373] In Example 10A, a two-fluid nozzle with a 1 mm tip size was used. The atomization air flow rate was 10 L / min. The fluids were pumped to the spray dryer at 6 mL / min using a syringe pump. The cyclone was set with an additional air flow rate of 150 L / min.

[0374] In Example 10B, an ultrasonic nozzle was used. The atomization air flow rate was 10 L / min. The fluid was pumped to the spray dryer at 6 mL / min using a syringe pump. The cyclone was set with an additional air flow rate of 150 L / min.

[0375] In Comparative Example 10C, spray drying was carried out using a Buchi B290 Spray Dryer equipped with a two-fluid nozzle with a tip size of 1.4 mm. The aspirator flow rate was set at 100% and the Q-flow setting was set at 40. Fluid was pumped into the spray dryer using a peristaltic pump at a speed setting of 35% (approximately 10 mL / min). The formed dry microcapsule powder was collected from a collection pot.

[0376] Other process settings are shown in Table 6 below.

[0377] [Table 8]

[0378] The spray drying experiments showed that the average particle size d of each of Examples 10A, 10B, and Comparative Example 10C was measured by laser diffraction according to the method therein. 50 Three free-flowing powders were produced with average particle sizes of 28.9, 40.8, and 9.1 microns. Note that in the case of the acid-treated vegetable protein encapsulates, the more dilute compositions dried with ultrasonic nozzles produced larger microcapsules. For the non-acid-treated vegetable proteins with similar solids content, the powders had a much smaller average particle size.

[0379] The vitamin D2 concentrations in the microcapsule powders were measured using method version B described herein and found to be 963 μg / g, 919 μg / g, and 1149 μg / g for Examples 10A, 10B, and Comparative Example 10C, respectively, which is close to the expected microcapsule target of 1000 μg / g and suggests very little loss of vitamin D2 during the spray drying process.

[0380] Example 11 - Accelerated stability study of Vitamin D2 microcapsules in a beverage formulation Beverage sample preparation The microcapsules of Examples 10A, 10B and Comparative Example 10C were each prepared into a concentrated slurry which could then be added to Miwadi Blackcurrant single concentrated squash.

[0381] 0.2g of each microcapsule was first suspended in 30g of boiling water with vigorous shaking, followed by vortexing at 2000 rpm for 1 minute to mimic the temperature profile during flash pasteurization. It was noted that the concentrated slurry prepared in Comparative Example 10C appeared cloudier and finer than Examples 10A and 10B. Figures 8a, 8b and 8c are 10x microscope images of the concentrated slurries of Examples 10A, 10B and Comparative Example 10C. The microcapsules of Examples 10A and 10B are visible and apparently survived the treatment. It is noteworthy that no intact microcapsules are visible in the image of Comparative Example 10C, which demonstrates that the microcapsules rapidly disintegrate when subjected to heat and shear. Instead, smaller aggregates of protein and very small particles of wax and vitamin D2 can be seen.

[0382] Accelerated Stability Testing The calculated mass of each concentrated slurry was added to 2 liters of squash and mixed with an overhead mixer at 800 rpm for 5 minutes to ensure homogeneity before transferring to bottles.

[0383] Each of the three squash samples was filled into a 200mL clear plastic PET bottle and the initial vitamin D2 loading was measured using the method described herein. The initial beverage vitamin D loadings of Examples 10A and 10B are shown in Table 7. However, in Comparative Example 10C, the initial measured beverage loading of vitamin D2 was undetectable. Without wishing to be bound by theory, this is believed to be due to the microcapsules breaking apart and releasing vitamin D2 in the concentrated slurry preparation in which the microcapsules were suspended and heated. The vitamin D2 oil floated to the top of the bottle and was not sampled.

[0384] The filled PET bottles of Examples 10A and 10B were then placed in a Binder KBF P 240-230V chamber set for accelerated ambient light stability testing at 20° C. and laboratory humidity (typically 50% relative humidity (RH)) with UV-A set at 1.1 W / m2. Vitamin D loading was measured again after 4 weeks in the Binder chamber. The % decrease in Vitamin D2 content was calculated and recorded in Table 7.

[0385] [Table 9]

[0386] After 4 weeks in squash, vitamin D2 in the encapsulates of the present invention was protected from degradation, so that in Example 10A, only 22.5% of the initial vitamin D2 was lost, and in Example 10B, only 5.5% of the initial vitamin D2 was lost. Unencapsulated vitamin D2 would be expected to degrade significantly when exposed to UV in this time frame, but this low level of loss demonstrated the protection provided by the microcapsules of the present invention. It can also be seen that the lowest loss was achieved with the larger average encapsulate size. Without wishing to be bound by theory, it is believed that the larger the average particle size of the encapsulate, the less degradation occurs because less surface area is available per mass of vitamin D2 for exposure to UV.

[0387] Example 12 - Encapsulation of natural pesticide actives Example 12A: Thymol Protein Microcapsule Preparation Preparation of protein hydrogels and application of shear to protein hydrogels The protein hydrogel shell was prepared and sheared as described in Example 8.

[0388] Protein solids were measured to be 9.3 wt%. Dilute acetic acid (3 wt% in DI water) was added to reduce the protein solids to 8.0%.

[0389] Preparation of spray-dried microcapsules The diluted dispersion was homogenized with a Silverson L5M-A high shear mixer (8000 rpm for 2 minutes). 16.81 g of thymol diluted to 40% by weight with Miglyol 812N was added to 103.25 g of the diluted dispersion. The mixture was further homogenized with the Silverson at 8000 RPM for 5 minutes. The droplet size was expected to be approximately 5 microns.

[0390] The samples were then spray dried using a Buchi B290 Spray Dryer. The air inlet temperature was 120°C with a Q flow rate setting of 40. A two-fluid nozzle with a 1.4 mm tip size was used. The aspirator flow rate was set at 100%. Fluids were pumped into the spray dryer using a peristaltic pump with a speed setting of 13% (4-5 mL / min).

[0391] The formed dry microcapsule powder was collected from the collection pot. The microcapsules were analyzed for their total thymol loading, which was found to be 4.9% by weight. The particle size was measured by laser diffraction and found to have a d50 of 23 microns.

[0392] Example 12B: Comparative Maltodextrin Thymol Microcapsule Preparation 45 g of maltodextrin was dissolved in 105 g of deionized water and mixed with a magnetic stir bar until a homogenous slurry was formed. 15.23 g of thymol diluted to 40% by weight with Miglyol 812N was added to the slurry along with 0.14 g of polysorbate 80. The mixture was homogenized with a Silverson L5M-A high shear mixer at 8000 rpm for 5 minutes.

[0393] The samples were then spray dried using a Buchi B290 Spray Dryer. The air inlet temperature was 130°C with a Q flow rate setting of 40. A two-fluid nozzle with a 1.4 mm tip size was used. The aspirator flow rate was set at 100%. Fluids were pumped into the spray dryer using a peristaltic pump with a speed setting of 13% (4-5 mL / min).

[0394] The dry microcapsule powder formed was collected from the collection pot. The microcapsules were analyzed for their total thymol loading, which was found to be 3.4% by weight. These microcapsules were so fragile that it was not possible to measure their particle size. When placed on a microscope slide with a cover glass, it could be seen that the weight of the cover was enough to break them.

[0395] Example 12C: Aqueous Release Test The thymol microcapsule powder of Example 12A was suspended in phosphate buffered saline (PBS) (pH 7.4) containing 0.2% w / v methylparaben and a solution of sodium acetate and calcium chloride according to Table 8, such that samples contained 4 mg of thymol. Duplicate samples were prepared so that samples could be analyzed at t=0 hours, 24 hours, 72 hours, 1 week, and 2 weeks of incubation.

[0396] [Table 10]

[0397] Samples were mixed on day 0 and placed in a 37°C incubator in the dark, except for the t=0 sample, which was analyzed immediately. At each time point, samples were centrifuged at 4900 RPM for 30 minutes and the supernatant transferred to a 50 mL Falcon tube. Ethanol was added to dilute the supernatant samples 10-fold. Thymol concentration in the supernatant was measured by gas chromatography and used to calculate the amount of thymol released from the microcapsules.

[0398] To the pelleted material after centrifugation of each sample, 2.9 mL of DI water and 0.1 mL of 10% KOH solution were added. The mixture was sonicated (Bandelin Sonopuls HD4200 with probe TS104) at 30% amplitude for 2 minutes, vortexed, and centrifuged at 4900 rpm for 5 minutes. 100 μL of the supernatant from each sample was diluted 10-fold with ethanol and the concentration of thymol was then measured by gas chromatography. This was used to calculate the amount of thymol remaining in the sample at the end of the experiment. The amount of thymol remaining was considered as the amount of thymol originally not released in the initial supernatant. The results are shown in Table 9.

[0399] [Table 11]

[0400] The release studies demonstrated that the majority of the active ingredient, i.e., more than 90%, remained encapsulated over a two week period. Such slurries are suitable for storage prior to application to fields and crops.

[0401] Example 12D: Comparative Maltodextrin-Thymol Release Study The thymol microcapsule powder of Comparative Example 12B was suspended in phosphate buffered saline (PBS) (pH 7.4) containing 0.2% w / v methylparaben according to Table 10 such that the sample contained 4 mg of thymol, the same level as Example 12A. There were only minor differences in the composition of the suspension which did not contain the insignificant low levels of NaOAc and CaCl2 in this example.

[0402] [Table 12]

[0403] Samples were prepared, mixed, and incubated for 1 hour. Samples were centrifuged at 4900 RPM for 10 minutes and the supernatant was transferred to a 50 mL Falcon tube. Ethanol was added to dilute the supernatant sample 10-fold. The thymol concentration in the supernatant was measured by gas chromatography and used to calculate the amount of thymol released from the capsules in buffered water.

[0404] To the pelleted material after centrifugation of the samples, 2.9 mL of deionized water and 0.1 mL of 10% KOH solution were added. The mixture was sonicated (Bandelin Sonopuls HD4200 with probe TS104) for 2 minutes at 30% amplitude, vortexed, and centrifuged at 4900 rpm for 5 minutes. 100 μL of the supernatant was diluted 10-fold with ethanol, and the concentration of thymol was then measured by gas chromatography. This was used to calculate the amount of thymol remaining in the samples at the end of the experiment. The amount of thymol remaining was considered as the amount of thymol originally not released in the initial supernatant. The results are shown in Table 11.

[0405] [Table 13]

[0406] This release study demonstrates that in maltodextrin microcapsules, more than 40% of the active ingredient is released in aqueous buffer after 1 hour in Comparative Example 12B. Such slurries are not suitable for storage before application to fields or crops. When prepared into an aqueous composition, or in the presence of water in the environment such as rain, it will release the active ingredient early, and therefore will not show sustained release properties.

[0407] Example 13 - Preparation of spray-dried microcapsules containing fragrance oil Fragrance / Solvent Mixtures Two different fragrances (13A and 13B) were prepared according to Table 12. Each fragrance was then blended with one of two solvents, either Miglyol® 812N or isopropyl myristate (IPM), in an 80:20 fragrance to solvent weight ratio.

[0408] Fragrance 13A was composed of only moderately volatile fragrance materials with similar volatility along with a range from very low to very high hydrophobicity. Fragrance 13B was composed of similar hydrophobic materials with a full range of volatility including low, medium and high volatility materials. Both fragrances had fragrance materials with HSP parameters ranging from δD of 15-20, δP of 1-7 and δH of 2.5-8.

[0409] [Table 14]

[0410] Preparation of spray-dried microcapsules A protein hydrogel slurry was made according to Example 8.

[0411] A first batch of fragrance composition was prepared as follows: A batch of 100-120 g of the protein hydrogel slurry of Example 8 was diluted to 20% with a 3% acetic acid solution to obtain a slurry with 8.0% protein solids by weight. The diluted slurry was then stirred in a 400 mL Nalgene beaker at 8000 rpm for 2 minutes using a Silverson lab mixer. 31.5% by weight (based on the weight of the slurry) of fragrance 13B / Miglyol® 812N blend was then added to the slurry and emulsified at 8000 rpm for an additional 5 minutes using a Silverson mixer to form a fine emulsion. The fine emulsion was aged at room temperature for approximately 2 days before being spray dried. This mixture was used in Experiment 2 TTB.

[0412] A second batch of fragrance composition was prepared as above, except that the fragrance blend was emulsified by gentle hand shaking immediately prior to spray drying rather than using a Silverson mixer. This mixture was used in Experiment 3 TTB.

[0413] A third batch of fragrance composition was prepared similar to the first batch, except that Miglyol® 812N was replaced with isopropyl myristate (IPM) to form the fragrance:solvent blend. The fragrance and slurry mixture was emulsified to form a fine emulsion using a Silverson mixer at 8000 rpm for an additional 5 minutes. The fine emulsion was aged at room temperature for about 2 days and then spray dried. This mixture was used in Experiment 6 TTB.

[0414] A fourth batch of fragrance composition was prepared with the same composition and in the same manner as the materials used in Experiment 6 TTB as well as the materials used in Experiment 7 CPB and Experiment 8 TTB.

[0415] The samples were spray dried using a ProCepT R&D Spray Dryer in its three column configuration: column height 1.8 m, column diameter 0.15 m.

[0416] To obtain a dry powder, the air inlet temperature was varied. The air inlet temperature was kept as low as possible to reduce the loss of volatile fragrance materials. The dry inlet air flow rate was 0.4 m 3 The spray dryer was kept constant at 4 mL / min. A two-fluid nozzle from Spray Systems was used with a 1.0 mm tip size. The atomization air flow rate was varied between experiments as shown in Table 13 below. The fluid was pumped into the spray dryer at 4 mL / min using a syringe pump in all experiments. An additional air flow rate of 150 L / min was introduced below the drying chamber to carry the air to the cyclone.

[0417] The dry microcapsule powder formed was collected in a collection pot and also from the interior surfaces of the equipment where it adhered, for example in the transfer pipe to the cyclone. The particle size of the microcapsules was measured by laser diffraction.

[0418] Fragrance 13B was successfully encapsulated as shown in Table 13.

[0419] [Table 15]

[0420] When dried at lower temperatures (inlet about 69°C), a maximum particle size of 30.1 microns was produced by the coarse fresh emulsion with Miglyol® 812N as the solvent, prepared immediately prior to spray drying. Changing the fragrance solvent from Miglyol® 812N to isopropyl myristate in the fine aged emulsion had little effect on particle size.

[0421] Decreasing the atomizing air flow rate resulted in larger particles (compare Run 8TT with Run 7CP).

[0422] The fragrance material composition of these microcapsules was analyzed using the GC fragrance loading quantification method described herein, and the results are shown in Table 14.

[0423] [Table 16]

[0424] Samples dried at lower air inlet temperatures typically had higher total fragrance loadings than those dried at higher air inlet temperatures.

[0425] When dried at lower temperatures (inlet about 69° C.), isopropyl myristate gave higher total loadings for the fine emulsions than Miglyol® 812N. In addition, at these drying conditions, the coarse emulsions gave higher loadings.

[0426] When the atomizing air flow rate was reduced and dried at higher temperatures (at least 80° C. at the inlet), higher total loadings were achieved than with higher air atomization.

[0427] Fragrance 13B demonstrated that for similar hydrophobic fragrance materials, materials with a range of volatility can be encapsulated. However, as expected, the least volatile fragrance materials were concentrated in the encapsulates, with benzyl salicylate constituting 48.4-56.3% of the fragrance compared to 20% of the fragrance before encapsulation. Drying with the crude emulsion at lower temperatures improved encapsulation of more volatile fragrance materials such as limonene from 0.6% to 1.5% of the fragrance.

[0428] Fragrance composition 13A was also successfully encapsulated, as shown in Table 15.

[0429] A first batch of fragrance composition was prepared as follows: A batch of 100g-120g of the protein hydrogel slurry of Example 8 was diluted to 20% by weight with 3% acetic acid solution to obtain a slurry with 8.0% protein solids by weight. The diluted slurry was then stirred in a 400mL Nalgene beaker at 8000 rpm for 2 minutes using a Silverson lab mixer. 28.3% by weight (based on the weight of the slurry) of composition 13B / Miglyol® 812N blend was then added to the slurry and emulsified at 8000 rpm for an additional 5 minutes using a Silverson mixer to form a fine emulsion. The fine emulsion was aged at room temperature for approximately 2 days before being spray dried. This mixture was used in Experiment 1 TTA.

[0430] A second batch of fragrance composition was prepared as described above. Immediately before use, 120g of the emulsion was diluted with 60g of 3% acetic acid solution under gentle stirring. This mixture was used in Experiment 9 TTA.

[0431] A third batch of fragrance composition was prepared in the same manner as the first batch above, except that the fragrance blend was sheared and emulsified immediately prior to spray drying rather than aging. This mixture was used in Experiment 3 TTA.

[0432] A fourth batch of fragrance composition was prepared as above, except that the fragrance blend was emulsified by gentle hand shaking immediately prior to spray drying rather than using a Silverson mixer. This mixture was used in Experiment 2 TTA.

[0433] A fifth batch of fragrance composition was prepared similar to the first batch, except that Miglyol® 812N was replaced with isopropyl myristate (IPM). This mixture was used in Experiment 4 TTA.

[0434] A sixth batch of fragrance composition was prepared in the same manner as the fifth batch, and this mixture was used in Test 5CPA.

[0435] The same equipment as in the previous experiment was used with the same dry air flow rate, emulsion flow rate and transport air flow rate as in the case of fragrance composition 13B. The dry microcapsule powder formed was again collected in a collection pot and also collected from the inside surfaces of the equipment where the dry microcapsule powder was attached, for example in the transport pipe to the cyclone. The particle size of the microcapsules was measured by laser diffraction.

[0436] [Table 17]

[0437] The largest particle size was produced using a coarse fresh emulsion with Miglyol® 812N as the fragrance solvent prepared immediately prior to spray drying.

[0438] The fine aged emulsion with Miglyol® 812N as the fragrance solvent produced the smallest microcapsule particle size. Dilution of the fine aged mature emulsion and operation at lower drying temperatures did not affect particle size. Changing the fragrance solvent from Miglyol® 812N to isopropyl myristate in the fine aged emulsion had little effect on particle size.

[0439] The fine emulsions that were aged and then spray dried had smaller particle size than the same freshly made emulsions.

[0440] The fragrance material composition of these microcapsules was analyzed using the GC fragrance loading quantification method described herein, and the results are shown in Table 16.

[0441] [Table 18]

[0442] All samples had similar total fragrance loadings, but the fine aged sample with IPM sprayed at the lower air atomization rate had the highest loading of 30%. This is significantly less than Fragrance Composition 13B, which had the highest total fragrance loading of 51%. Without wishing to be bound by theory, this is likely due to the presence of very low logP fragrance materials in Fragrance 13A.

[0443] Fragrance Composition 13A contained four fragrance materials of similar medium volatility and varying hydrophobicity, demonstrating the ability to encapsulate materials with a range of hydrophobicity. The encapsulated fragrance compositions contained more dodecanenitrile, the most hydrophobic fragrance material, for all examples, which was least noticeable in the coarse emulsion samples.

[0444] Delta-damascone was the least concentrated fragrance material, despite having a higher logP than geraniol and undecavertol. These two alcohols were well encapsulated (especially geraniol), demonstrating that it is still possible to encapsulate these relatively hydrophilic fragrance materials within a fragrance.

[0445] Olfactory evaluation of spray-dried microcapsules A concentrated slurry of microcapsules from Test 3TTA was prepared prior to making diluted formulations for olfactory evaluation. To obtain a slurry paste, some 1x buffer containing preservative was added dropwise to the dry microcapsules in a 50mL Falcon tube, vortexing at 2000 rpm between additions. Once the paste appeared homogenous, more buffer was added for further dilution, using further vortexing as a means to ensure homogenous dispersion of the microcapsules. The suspension was left for 1 hour to allow the microcapsules to swell, and then strained through a 40μm cell strainer for 5 minutes. Any excess water was absorbed with tissue paper.

[0446] The total fragrance level was analyzed by GC according to the method described herein and was 12.6% by weight. This is lower than the total fragrance level of spray-dried microcapsules. Without wishing to be bound by theory, it is believed that the hydrogel shell hydrates and swells, causing the shell to increase in mass. In addition, a small amount of surface fragrance may be lost in the water phase.

[0447] A dilute slurry of microcapsules containing gellan gum was prepared containing 0.1% total fragrance by weight for olfactory evaluation. Gellan gum helps to keep the microcapsules well suspended. A solution of gellan gum was prepared by mixing 9.5 mg of gellan gum with 15 g of deionized water in a 50 mL Falcon tube. The mixture was heated above 90°C for 20 minutes and stirred at 500 rpm using an Eppendorf Thermomixer C set at 100°C. After cooling to room temperature, 15 g of double strength buffer was added. Using a micropipette with a low shear tip, the concentrated encapsulate slurry was added to the gellan gum solution, the sample tube was closed, and mixed by repeated inversion.

[0448] The pH of the diluted slurry was 3.05. The odor of the diluted slurry was evaluated according to the methods described herein and the results are shown in Table 17.

[0449] [Table 19]

[0450] Upon initial application, there was a strong characteristic odor of the fragrance, indicating that some of the fragrance oil was bound to the surface of the hydrogel shell. After 24 hours of drying, the odor was very weak, indicating that most of the surface fragrance had evaporated. When rubbed or pressed on glass, a strong characteristic odor was noted as the force ruptured the microcapsules, releasing the fragrance. When rubbed on card, the odor was of medium intensity and the fragrance characteristics were somewhat different from those on glass, indicating that the encapsulated fragrance had only been partially released.

[0451] Example 14 - Crosslinking of spray-dried fragrance microcapsules Spray dried microcapsules were prepared as in Example 13, Experiment 3TTA.

[0452] Hard water adjusted to pH 3 was added dropwise to 0.8 g of dried microcapsules in a 50 mL Falcon tube, vortexing at 2000 rpm between additions. Once the paste appeared homogenous, more pH 3 hard water was added for further dilution, using further vortexing as a means to ensure homogenous dispersion of the microcapsules. The suspended microcapsules were further diluted with a total of 390 mL of hard water, and the pH was adjusted to 3.0±0.5.

[0453] A 10 wt% tannic acid solution was prepared by manually shaking and vortexing for a few seconds using a Fisherbrand™ ZX4 IR Vortex Mixer, followed by immersion in an ultrasonic bath set at 50° C. for 5-10 minutes until completely dissolved.

[0454] 10.6 g of tannic acid solution was added to the microcapsule suspension under mechanical stirring at 170 rpm at 50° C. and stirred for 5.5 hours. After this, the suspension was stored in a refrigerator for about 36 hours. The crosslinked microcapsule suspension was sieved through a 38 μm sieve, washed with pH 3 hard water, and resuspended in a clean separatory funnel in pH 3 hard water. The decanted capsules were collected a second time through a 38 μm sieve, washed with 1× buffer containing preservative, and resuspended in this buffer in a separatory funnel. The capsules were collected as a concentrated slurry after decantation and had a brown microencapsulated appearance, indicating that crosslinking had occurred.

[0455] The crosslinked capsule slurry was directly filtered through a 40 μm cell strainer for 5 minutes, and excess water was absorbed with tissue paper. The total fragrance level was analyzed by GC according to the method herein and found to be 4.1 wt.%, which is lower than the total fragrance level of the microcapsules before crosslinking. Without wishing to be bound by theory, this is believed to be due to surface-bound and loosely bound fragrance that is removed by the washing process during crosslinking. Particle size was measured by laser diffraction and found to be D 50The particle size was 47.9 μm, which is larger than the particle size of the original spray dried encapsulates, indicating that the hydrogel shell had hydrated and the encapsulates had swelled.

[0456] Olfactory evaluation of spray-dried and cross-linked microcapsules A dilute slurry of microcapsules containing gellan gum was prepared to contain 0.1% by weight total fragrance. The gellan gum helped to keep the microcapsules well suspended. This was done according to the method of Example 13. The pH of the dilute slurry was 3.04. The odor of the dilute slurry was evaluated according to the method described herein, and the results are shown in Table 18.

[0457] [Table 20]

[0458] Upon initial application, there was a moderate characteristic odor of the fragrance, indicating that a small amount of the fragrance was bound to the surface of the hydrogel shell. After 24 hours of drying, the odor was very weak, indicating that most of the fragrance on the surface had evaporated. When rubbed or pressed on glass, a strong characteristic odor was noted as the force caused the microcapsules to burst and release the fragrance. When rubbed on card, a moderate odor was noted and the fragrance characteristics were similar to those on glass.

[0459] Example 15 - Preparation of spray-dried microcapsules containing linseed oil Preparation of protein hydrogels and application of shear to protein hydrogels A protein hydrogel slurry was prepared as described in Example 8. Protein solids were measured to be 9.5% by weight.

[0460] Preparation of spray-dried microcapsules Flaxseed oil is a dietary supplement used for its high levels of omega-3 fatty acids that is also a vegan alternative to fish oil. The slurry was homogenized using a Silverson L5M-A high shear mixer at 8000 rpm for 2 minutes. Flaxseed oil was added to the slurry at a 1:1 oil to protein solids weight ratio, and the mixture was further homogenized using a Silverson at 8000 RPM for 5 minutes to create a fine emulsion.

[0461] The slurries were spray dried within one day of preparation using a Buchi B290 Spray Dryer using a two-fluid nozzle with a 1.4 mm tip size. The aspirator flow rate was set at 100% and the Q-flow setting was 40. The fluids were pumped into the spray dryer using a peristaltic pump at a speed setting of 13% (4-5 mL / min). The air inlet temperature was varied from 183-180 °C and the air outlet temperature was varied from 126-122 °C.

[0462] A dry microcapsule powder was formed, indicating that the oil was efficiently encapsulated. The particle size was measured by laser diffraction according to the method herein and found to have a d50 of 45.3 microns. The powder had no rancid off-odor, indicating that the temperature in the dryer did not degrade the linseed oil. It had a weak nutty odor and a very slight vinegar odor, indicating that only low levels of surface oil were present.

[0463] FIG. 9 shows a 10x optical microscope image of Example 15 suspended in 1x citrate buffer, where it can be seen that the encapsulates remain intact.

[0464] The microcapsule powder of Example 15 was also suspended in Miwadi blackcurrant 1x concentrate at a concentration of 12.5g / L by vortexing at 2000rpm for 1 minute. The encapsulation did not impart any negative odor to the characteristic red fruit note of the original product, demonstrating that the encapsulation is insoluble and the linseed oil remains encapsulated, thereby having little effect on the product aroma. In comparison, the same level of linseed oil cannot be incorporated into beverages without emulsifiers, which would impart a very pronounced nutty odor and characteristic effect on the taste of the beverage.

[0465] Example 16 - Demonstration of protein gel formation Reverse osmosis (RO) water and pea protein isolate were added to a 1 liter stainless steel vessel, placed in a 92°C water bath and mixed at 1300 rpm using an overhead stirrer. After stirring for 3 minutes, glacial acetic acid was added. The mixture was stirred at 1300 rpm for a total of 45 minutes, ensuring that the temperature remained above 80°C. The mixture was then subjected to high shear using a Silverson L5M-A homogenizer at 8000 rpm for 10 minutes. 20 mL aliquots of the liquid were poured into 50 mL Falcon tubes, sealed and refrigerated overnight in the normal upright position.

[0466] Different levels of organic acids were tested, as listed in Table 19.

[0467] [Table 21]

[0468] After a minimum of 12 hours of refrigeration, gel formation was assessed by inverting the vials. As can be seen in Figure 10, the use of 30% and 10% glacial acetic acid resulted in the formation of solid gels that did not fall under gravity. When 1% glacial acetic acid, but no acid, was used, no gel was formed and fell into the inverted Falcon tube lid.

Claims

1. A method for the preparation of biodegradable microcapsules comprising the steps of: (a) forming a solution comprising one or more plant-derived proteins in a solvent system, said solvent system comprising miscible co-solvents, a first co-solvent increasing the solubility of said plant-derived proteins and a second co-solvent decreasing the solubility of said plant-derived proteins, said co-solvents being added to said solution in either concentrated or diluted form, preferably wherein the pH of said plant-derived protein solution is at least 0.5 pH units lower than the isoelectric point of said plant-derived proteins; (b) inducing the plant-derived protein in the solution to undergo a sol-gel transition to form a plant-derived protein hydrogel; (c) subjecting the plant-derived protein hydrogel to a shear treatment to form a plant-derived protein hydrogel slurry; (d) dispersing an active ingredient in the plant-derived hydrogel slurry to form a composition; (e) drying the composition, thereby evaporating at least a portion of both the first and second co-solvents to form microcapsules.

2. 2. The method of claim 1, wherein the plant-derived protein is selected from pea protein, potato protein, rapeseed protein, lentil protein, chickpea protein, broad bean protein, mung bean protein, sunflower seed protein, pumpkin seed protein, flax protein, chia protein, canola protein, lupin protein, alfalfa protein, moringa protein and / or rice protein, preferably selected from pea protein and / or potato protein.

3. 3. The method of claim 1 or 2, wherein the first co-solvent is an organic acid, preferably wherein the organic acid is acetic acid, lactic acid, formic acid, gluconic acid, propionic acid, an alpha-hydroxy acid, and / or a beta-hydroxy acid, more preferably lactic acid or acetic acid, and wherein the first co-solvent is present in the solution of step (a) at a concentration on a weight % basis equal to or greater than the concentration of protein solids.

4. 4. The method according to any one of claims 1 to 3, wherein the second co-solvent is selected from water, ethanol and / or ethyl acetate, more preferably selected from water and / or ethanol, even more preferably water.

5. 5. The method of any one of claims 1 to 4, wherein in step (b), the protein solution is heated to a first temperature higher than the sol-gel transition temperature of the one or more plant-derived protein solutions and then reduced to a second temperature lower than the sol-gel transition temperature of the one or more plant-derived protein solutions to form a hydrogel.

6. The shearing treatment comprises a single shearing step involving fragmenting the plant derived protein hydrogel into fragments, preferably the fragments have a diameter of 0.5 to 50 microns, preferably 1 to 40 microns, preferably 2 to 30 microns as determined by laser diffraction. 50 The method according to any one of claims 1 to 5, comprising:

7. The method according to any one of claims 1 to 5, wherein the shearing treatment comprises a first shearing step followed by a second shearing step.

8. 8. The method of claim 7, wherein the first shearing step involves fragmenting the plant derived protein hydrogel into fragments, and preferably at least 80% by weight of the fragments produced in the first shearing step have particle sizes in the range of 1 mm to 100 mm, preferably 1 mm to 50 mm, preferably 1 mm to 30 mm, more preferably 10 mm to 30 mm, more preferably 15 mm to 30 mm, even more preferably 20 mm to 30 mm, as measured by optical microscopy.

9. The second shearing step involves further fragmenting the plant derived protein hydrogel, and preferably the fragments produced in the second shearing step have a diameter of 0.5 to 50 microns, preferably 1 to 40 microns, preferably 2 to 30 microns, as determined by laser diffraction. 50 9. The method according to claim 7 or 8, comprising:

10. 10. The method according to any one of claims 7 to 9, wherein step (c) further comprises subjecting the plant-derived protein hydrogel slurry to a solvent reduction step, preferably a solubilizing solvent reduction step, between the first shearing step and the second shearing step.

11. The solvent reduction step comprises: (i) contacting the fragments of the plant-derived hydrogel slurry with a non-solubilizing solvent; (ii) separating the fragments of the plant-derived hydrogel slurry from the non-solubilizing solvent to obtain a washed plant-derived protein hydrogel slurry; (iii) optionally repeating steps (i) and (ii).

12. 12. The method of any one of claims 1 to 11, further comprising altering the pH of the plant-derived protein hydrogel slurry so that it differs from the isoelectric point of the plant-derived protein by more than 1 pH unit.

13. 13. The method of claim 12, wherein the step of altering the pH of the plant-derived protein hydrogel slurry occurs after or consecutively with step (c).

14. The method of any one of claims 1 to 13, wherein the composition formed in step (d) is a shear thinning composition.

15. The composition formed in step (d) is heated at 20° C. and 50 s -1 Viscosity in the range of 1 to 10,000 cP at 20° C. and 50 s -1 Viscosity in the range of 10 to 7500 cP at 20° C. and 50 s -1 The method of any one of claims 1 to 14, wherein the composition has a viscosity in the range of 15 to 5000 cP at 100°C.

16. 16. A method according to any one of the preceding claims, wherein the composition formed in step (d) has a protein solids content in the range of from 1% to 25% by weight, preferably from 2% to 20% by weight, more preferably from 4% to 15% by weight, even more preferably from 5% to 12% by weight based on the total weight of the composition.

17. 17. The method of any one of claims 1 to 16, wherein the active ingredient is selected from vitamins, minerals, flavor materials, fragrance materials, pro-flavors, pro-fragrances, flavor enhancers, malodor counteractants, nutritional supplements, living organisms (e.g., probiotics), pharmaceuticals, antibacterial agents, antiviral agents, anti-inflammatory agents, insecticides, herbicides, fertilizers, fungicides, insecticides, animal repellents, anti-acne agents, skin brighteners, skin emollients, skin moisturizers, wrinkle control agents, fabric softener actives, surface cleaning actives, skin conditioning agents, hair conditioning agents, dyes, pigments, and adhesives, or combinations thereof.

18. the active ingredient is at least one fragrance or flavor material; the at least one fragrance or flavor material has a vapor pressure of 0.00001 Torr or greater at 25° C.; and / or 18. The method of claim 17, wherein said at least one fragrance or flavour material has a log P of 3.0 or greater, preferably 3.5 or greater, more preferably 4.0 or greater.

19. 18. The method of claim 17, wherein the active ingredient is at least one fragrance or flavor material that is part of a fragrance or flavor, preferably the fragrance or flavor contains at least 20% by weight, based on the total weight of the fragrance or flavor, of fragrance or flavor material having a log P of 3.0 or greater, more preferably 3.5 or greater, more preferably 4.0 or greater.

20. 18. The method according to claim 17, wherein the active ingredient is a vitamin or mineral, preferably selected from vitamin A, vitamin B1, vitamin B2, vitamin B3, vitamin B5, vitamin B6, vitamin B7, vitamin B9, vitamin B12, vitamin C, vitamin D, vitamin E, vitamin K, magnesium, sodium, potassium, zinc, iron, calcium, iodine, linseed oil, omega-3 fatty acids, folic acid, thiamine, riboflavin, niacin and phosphorus, or mixtures thereof, more preferably vitamin D.

21. A method according to any one of claims 1 to 20, wherein the active ingredient is part of a composition comprising the active ingredient and an active carrier phase.

22. 22. The method according to any one of claims 21, wherein the active carrier phase is a solvent, a fat or a wax.

23. The composition formed in step (d) comprises droplets of the active ingredient or the composition comprises droplets of the active ingredient and a diameter of 0.5 to 50 microns, preferably 1 to 40 microns, preferably 2 to 30 microns, as measured by laser diffraction. 50 and an active carrier phase having the formula:

24. 24. The method according to any one of the preceding claims, wherein plant-derived protein residues formed during step (e) but not incorporated into the microcapsules are recycled in the method, preferably added back to step (a).

25. 25. The method according to any one of claims 1 to 24, further comprising subjecting the microcapsules to a post-treatment step, preferably wherein the post-treatment step comprises a non-covalent cross-linking step, a covalent cross-linking step or a coating formation step.

26. Biodegradable microcapsules obtained or obtainable by the method according to any one of claims 1 to 25.

27. 1. A method for the preparation of a biodegradable microcapsule composition, comprising: (a) preparing biodegradable microcapsules according to the method of any one of claims 1 to 25; (b) suspending the biodegradable microcapsules in an external phase.

28. 28. A biodegradable microcapsule composition obtained or obtainable by the method of claim 27.

29. 1. A biodegradable microcapsule comprising an active ingredient and a plant-derived protein carrier comprising a plant-derived protein, said plant-derived protein carrier encapsulating said active ingredient, said plant-derived protein having a solubility of less than 50% when measured at a protein concentration of 5% w / w in an aqueous solution at pH 7 and 25°C.

30. 30. The biodegradable microcapsules of claim 29, wherein at least 25%, more preferably at least 40%, even more preferably at least 50%, and even more preferably at least 60% of the initially encapsulated active ingredient remains present within the microcapsules after incubation in water at 20°C for 10 days as measured by HPLC.

31. 31. Biodegradable microcapsules according to claim 29 or 30, wherein the plant-derived protein is selected from pea protein, potato protein, rapeseed protein, lentil protein, chickpea protein, broad bean protein, mung bean protein, sunflower seed protein, pumpkin seed protein, flax protein, chia protein, canola protein, lupin protein, alfalfa protein, moringa protein and / or rice protein, preferably selected from pea protein and / or potato protein.

32. The plant-derived protein is pretreated with an organic acid, preferably the organic acid is acetic acid, lactic acid, formic acid, propionic acid, α-hydroxy acid and / or β-hydroxy acid, more preferably lactic acid or acetic acid. The biodegradable microcapsule according to any one of claims 29 to 31.

33. 33. The biodegradable microcapsule of any one of claims 29 to 32, wherein the active ingredient is selected from vitamins, minerals, flavor materials, fragrance materials, pro-flavors, pro-fragrances, flavor enhancers, malodor counteractants, nutritional supplements, living organisms (e.g., probiotics), pharmaceuticals, antibacterial agents, antiviral agents, anti-inflammatory agents, insecticides, herbicides, fertilizers, fungicides, insecticides, animal repellents, anti-acne agents, skin brighteners, skin emollients, skin moisturizers, wrinkle control agents, fabric softener actives, surface cleaning actives, skin conditioning agents, hair conditioning agents, dyes, pigments, and adhesives, or combinations thereof.

34. the active ingredient is at least one fragrance or flavor material; the at least one fragrance or flavor material has a vapor pressure of 0.00001 Torr or greater at 25° C.; and / or 34. The biodegradable microcapsule of claim 33, wherein the at least one fragrance or flavour material has a log P of 3.0 or greater, preferably 3.5 or greater, more preferably 4.0 or greater.

35. 34. The biodegradable microcapsule of claim 33, wherein the active ingredient is at least one fragrance or flavor material that is part of a fragrance or flavor, preferably the fragrance or flavor contains at least 20% by weight, based on the total weight of the fragrance or flavor, of fragrance or flavor material having a log P of 3.0 or more, more preferably 3.5 or more, more preferably 4.0 or more.

36. 34. The biodegradable microcapsules according to claim 33, wherein the active ingredient is a vitamin or mineral, preferably selected from vitamin A, vitamin B1, vitamin B2, vitamin B3, vitamin B5, vitamin B6, vitamin B7, vitamin B9, vitamin B12, vitamin C, vitamin D, vitamin E, vitamin K, magnesium, sodium, potassium, zinc, iron, calcium, iodine, linseed oil, omega-3 fatty acids, folic acid, thiamine, riboflavin, niacin and phosphorus, or mixtures thereof, more preferably vitamin D.

37. 37. The biodegradable microcapsule of any one of claims 29 to 36, wherein the active ingredient is part of a composition comprising the active ingredient and an active carrier phase.

38. 38. The biodegradable microcapsule of claim 37, wherein the active carrier phase is a solvent, a fat or a wax.

39. The microcapsules have a d of 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, or 10 μm or less, as measured by laser diffraction. 50 The biodegradable microcapsule according to any one of claims 29 to 38, comprising:

40. 40. The biodegradable microcapsule of any one of claims 29 to 39, wherein the plant-derived protein has a protein secondary structure having at least 40% intermolecular beta-sheets, at least 50% intermolecular beta-sheets, at least 60% intermolecular beta-sheets, at least 70% intermolecular beta-sheets, at least 80% intermolecular beta-sheets, or at least 90% intermolecular beta-sheets, wherein the % intermolecular beta-sheet content is measured by FTIR.

41. 41. The biodegradable microcapsule of any one of claims 29 to 40, wherein the plant derived protein carrier is non-covalently modified by a non-covalent cross-linking agent, or the plant derived protein carrier is covalently modified by a covalent cross-linking agent, or the plant derived protein carrier has a coating deposited thereon.

42. 42. The biodegradable microcapsule according to any one of claims 29 to 41, wherein the plant-derived protein is pea protein and the active ingredient is vitamin D.

43. A composition comprising a biodegradable microcapsule according to any one of claims 29 to 42 and an external phase.

44. A formulated product comprising the biodegradable microcapsules according to any one of claims 29 to 42.

45. (a) producing biodegradable microcapsules by the method according to any one of claims 1 to 25; (b) mixing the biodegradable microcapsules with a product formulation.

46. Use of the biodegradable microcapsules according to any one of claims 29 to 42 in a formulated product.

47. 47. The method of claim 45 or the use of claim 46, wherein the formulated product is a food, a beverage, a cosmetic, a home care product, a personal care product, a pharmaceutical, an industrial product (e.g., paint, adhesive, sandpaper, tape, etc.), a medical device, a biomaterial, or a pesticide.

Citation Information

Patent Citations

  • Encapsulated phospholipids - stabilized oxidizable materials

    JP2009519980A

  • Dried Rehydratable Composition

    US20200060957A1

  • Protein microcapsules and method of preparing the same

    WO2020131879A2

  • Plant based functional materials

    WO2020177881A1

  • Plant based functional materials

    WO2020178448A1